GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 126115198 species occurrences available in GBIF matching the query: BasisOfRecord: Specimen. The dataset includes 126115198 records from 4763 constituent datasets: 11900 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 23 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 251554 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 288 records from Estudio de la distribución geográfica de Peromyscus ochraventer y análisis de su variabilidad cromosómica. 2 records from Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae). 2 records from Shewanella marisflavi sp. nov. and Shewanella aquimarina sp. nov., slightly halophilic organisms isolated from sea water of the Yellow Sea in Korea. 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 775 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 1 records from Arthropoden aus südostalpinen Höhlen.. 447 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 116410 records from Naturalis Biodiversity Center (NL) - Crustacea. 1 records from The rare deep-living hyperiid amphipod Megalanceoloides remipes (Barnard, 1932): complementary description and symbiosis. 6 records from Hemichordata collection of National Museum of Nature and Science. 8934 records from El género Bursera en México. Parte II. 90 records from A taxonomic revision of the genus Diplonevra Lioy (Diptera: Phoridae) from China. 15300 records from Base de datos de colecciones de maíces nativos, teocintles y Tripsacum de México. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 8 records from Galeus corriganae sp. nov., a new species of deepwater catshark (Carcharhiniformes: Pentanchidae) from Papua New Guinea. 5549 records from Diplopoda (NSMK-DI). 97 records from DMNH Eggs. 291 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Huevos (MFA-ZV-Or-Hu). 13504 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 10616 records from Evaluación estacional de la fauna ictiológica, malacológica y flora ficológica de la Reserva de la Biósfera El Vizcaino, BCS, Fase I: Laguna Ojo de Liebre. 1490 records from A comprehensive checklist of earthworm species and subspecies from Vietnam (Annelida: Clitellata: Oligochaeta: Almidae, Eudrilidae, Glossoscolecidae, Lumbricidae, Megascolecidae, Moniligastridae, Ocnerodrilidae, Octochaetidae). 35 records from Zanobatus maculatus, a new species of panray from the Gulf of Guinea, eastern central Atlantic (Elasmobranchii: Batoidea: Zanobatidae). 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 398 records from Tsetse flies of East Africa update. 31917 records from Mollusca of Costa Rica (INBio). 2 records from A new legskate, Sinobatis andamanensis (Rajiformes: Anacanthobatidae), from the Andaman Sea (northeastern Indian Ocean). 375 records from Phthiraptera. 168515 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 58475 records from Oregon State University Herpetological Collection. 8 records from Ortopthera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 11 records from Redescription of the rare and endangered Broadfin Shark Lamiopsis temminckii (Müller & Henle, 1839) (Carcharhiniformes: Carcharhinidae) from the northeastern Arabian Sea. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 2 records from Cathorops festae (Boulenger 1898) (Siluriformes; Ariidae), a valid species from Ecuador and Peru. 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 142 records from Tejidos de quirópteros de tres localidades del caribe colombiano. 13 records from Bryozoa of the British Isles. 814 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 3104 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 14 records from Contribution to the knowledge of Neoperla (Plecoptera: Perlidae) from Hainan Province of China. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 13089 records from Ghent University - Zoology Museum - Vertebrate collection. 10730 records from Specimens of lichen herbarium KPABG. 336 records from Macroarthropods, Isua 2013, Greenland. 161214 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 815 records from Listado taxonómico de la ictiofauna de la costa de Michoacán. 5 records from Arthropoden aus südostalpinen Höhlen.. 7 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 5953 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 241 records from Asociación de cactáceas con arbustos en el desierto costero de Topolobampo, Sinaloa. 22 records from Taxonomic review of the genus Zethus Fabricius (Hymenoptera: Vespidae: Eumeninae) from Vietnam with descriptions of four new species. 258 records from The Glyptothorax of Sundaland: a revisionary study (Teleostei: Sisoridae). 215 records from The Diptera Site. 295 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 315232 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 10072 records from Guadeloupe_Herbier. 6859 records from Plan de vertebrados de la Patagonia. 1647890 records from International Barcode of Life project (iBOL). 14865 records from SUI Vertebrate Collection. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 87 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 3 records from A new species of the genus Ectemnius Dahlbom, 1845 from Cameroon (Hymenoptera: Crabronidae). 6 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 33 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 134 records from Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family. 24 records from A revision of the Indo-Pacific fish genus Caragobius (Gobiidae: Amblyopinae).. 1 records from Nothrus spinifer. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 30 records from A new river loach from the main channel of the upper Mekong in Yunnan (Cypriniformes: Nemacheilidae). 15 records from Discontinuous color variation in the assassin bug species Tiarodes miyamotoi (Hemiptera: Reduviidae: Reduviinae). 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 14364 records from JOI - Herbário Joinvillea. 2312 records from Mycological collection of the National Museum. 2476 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 1650 records from University of Calgary Herbarium. 1 records from A new macropterous species of a rarely collected subfamily (Heteroptera, Tingidae, Vianaidinae). 1613 records from Biodiversidad asociada a mantos de rodolitos y praderas de pastos marinos en Bahía Concepción, BCS. 27 records from Redescription of Apteronotus mariae (Eigenmann & Fisher, 1914) and the taxonomic status of Apteronotus jurubidae (Fowler, 1944) (Gymnotiformes: Apteronotidae).. 10 records from Two new species of Ankareus Kerremans (Coleoptera: Buprestidae: Haplostethinae) from southern Africa. 31 records from Siphonaptera. 5 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 22111 records from OEH Atlas of NSW Wildlife. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 25 records from Description of three new species of the genus Chromaphyosemion Radda, 1971 (Cyprinodontiformes: Nothobranchiidae) from the coastal plains of Cameroon with a preliminary review of the Chromaphyosemion splendopleure complex.. 12161 records from ISE - Herbário ISE. 6 records from A new species of salamander of the genus Hynobius (Amphibia, Caudata, Hynobiidae) from South Korea. 5098 records from Atlas de los coleóptera Scarabaeoidea de México. Segunda parte. 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 2 records from A new iphiculid crab (Crustacea, Brachyura, Leucosioidea) from the Middle Miocene of Austria, with notes on palaeobiogeography of Iphiculus. 8 records from Dendrogramma, New Genus, with Two New Non- Bilaterian Species from the Marine Bathyal of Southeastern Australia (Animalia, Metazoa incertae sedis) – with Similarities to Some Medusoids from the. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 424 records from The types of Phasmida in the Natural History Museum, London, UK. 787 records from List of Spiders of Prioksko-Terrasnyi Biosphere Reserve. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 592 records from A global database for the distributions of crop wild relatives. 167 records from A Review of the Jumping Spider Fauna (Araneae: Salticidae) of Chile. 5 records from Two new species of the genus Phaea Newman, 1840 (Coleoptera: Cerambycidae) from Mexico. 2 records from Description of the first Oriental species of the ant genus Xymmer (Hymenoptera: Formicidae: Amblyoponinae). 2 records from Plectranthias takasei, new species of anthiadine fish from southern Japan (Teleostei: Serranidae). 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 68 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 16 records from The Steninae MacLeay, 1825 (Coleoptera: Staphylinidae) of Iran: identification key, checklist of species and a new synonymy. 2 records from On the type locality of Sorubim trigonocephalus Miranda-Ribeiro, 1920 (Siluriformes: Pimelodidae). 2 records from Enchelycore nycturanus, a new moray eel from South Africa (Teleostei: Anguilliformes: Muraenidae).. 19 records from Copepods (Cyclopoida) associated with top shells (Vestigastropoda: Trochoidea: Tegulidae) from coastal waters in southern Japan, with descriptions of three new species. 2 records from Description of a new species of Lethe (Lepidoptera, Nymphalidae, Satyrinae) from western Yunnan, China. 12289 records from ISM Mammalogy Collection. 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 168966 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2 records from Palaearctic Hoplitis bees of the subgenera Formicapis and Tkalcua (Megachilidae, Osmiini): biology, taxonomy and key to species. 2649 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 5 records from Redescription of the poorly known crab spider Xysticus spasskyi (Araneae: Thomisidae). 1229 records from Insect Collection (CeStuBio). 1 records from Celaeno plicata. 24132 records from Computarización de abejas de la colección entomológica de la Frontera Sur. 78 records from The Mysidae (Crustacea: Peracarida: Mysida) in fresh and oligohaline waters of the Mediterranean. Taxonomy, biogeography, and bioinvasion. 23443 records from HUEM - Herbário da Universidade Estadual de Maringá. 4296 records from Diversidad de hemíptera: heteróptera de Baja California e islas del Golfo de California. 1877 records from Ims fish tag database. 67 records from Kirkegaardia (Polychaeta, Cirratulidae), new name for Monticellina Laubier, preoccupied in the Rhabdocoela, together with new records and descriptions of eight previously known and sixteen new species from the Atlantic, Pacific, and Southern Oceans. 7735 records from CSUC Vertebrate Collection. 70494 records from HUFU - Herbarium Uberlandense. 1 records from Hoplophora globosa. 20 records from Heteroptera - SMNG. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 454 records from Copépodos pelágicos del Pacífico norte mexicano. 9 records from A new species of the genus Aphanius (Nardo, 1832) (Actinopterygii, Cyprinodontidae) from Algeria.. 33 records from Revision von Suctobelba trigona (Michael, 1888). 1030627 records from Phanerogamic Botanical Collections (S). 20 records from Truchas Mexicanas. 20043 records from Mollusca collection of National Museum of Nature and Science. 113 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 68861 records from African Rodentia. 271740 records from MVZ Herp Collection (Arctos). 28792 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 65 records from A new species of Rineloricaria (Siluriformes: Loricariidae) from the Paraná and Uruguay River basins, Misiones, Argentina.. 2 records from Two new species of the genus Deontolaimus de Man, 1880 (Nematoda: Leptolaimidae) from mangrove ecosystems of Vietnam. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 1 records from Damaeus concolor. 7 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 1 records from Un chilopode cavernicole nouveau de Yougloslavie Bothropolys magnificus n. sp.. 62283 records from PRECIS (KwaZulu-Natal Herbarium). 5709 records from Coleoptera of Piska Forest. 712 records from Herbier G. Garapin (BOUM). 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 109404 records from University of Vienna, Institute for Botany - Herbarium WU. 9302 records from Ants from the Paraguayan dry Chaco. 379 records from WNMU Fish Collection (Arctos). 9889 records from UConn Mammals. 44 records from Colección e identificación de las especies de Meloidogyne y su distribución en los cultivos más importantes para México. 3811 records from Captura de datos de la Colección de Curculionoidea (Insecta: Coleoptera) de la Universidad Autónoma de Querétaro. 5147 records from Códigos de barras de la vida en peces y zooplancton de México. 25 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 6 records from Two new species of the rare genus Nygolaimoides Meyl in Andrássy, 1960 (Nematoda, Dorylaimida, Thorniidae) from Iran, with a compendium of its species. 26385 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 1 records from Nothrus runcinatus. 16685 records from UFG - Herbário da Universidade Federal de Goiás. 5 records from A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica. 1702 records from BioGIS - Bryophytes - HUJ collections. 6039 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 19 records from Four subgenera of Bracon Fabricius (Hymenoptera, Braconidae, Braconinae) newly recorded from China, with description of five new species. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 77 records from ZUEC-AST - Coleção de Asteroidea do Museu de Zoologia da UNICAMP. 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 1353 records from Colección de Entomología - Diptera - Ceratopogonidae. 603 records from Registros preliminares del "Catálogo de cangrejos ermitaños del mar Caribe colombiano". 6 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 3592 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 2 records from A unique new genus and species of the phyline plant bug tribe Hallodapini from the Philippines and Thailand (Hemiptera: Heteroptera: Miridae: Phylinae: Hallodapini). 16346 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 10 records from Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae.. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 233224 records from MVZ Mammal Collection (Arctos). 1333 records from Inventario computarizado de la colección de parásitos de peces del noroeste de México. 10075 records from Nematoda of Costa Rica (INBio). 123404 records from Australian National Wildlife Collection provider for OZCAM. 1 records from Zetes longiusculus. 689 records from Computarización de la Colección nacional del phylum Porifera Gerardo Green. 32 records from Sea Ice Nematodes. 12499 records from WhiteSeaPlankton. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 24 records from Transferred depository for twenty-seven holotypes of the plant bug and flower bug species recently described from Thailand (Hemiptera: Heteroptera: Miridae and Anthocoridae). 22213 records from Coleção de Aves do Museu Nacional / UFRJ. 1 records from Oppia glaucina. 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 180 records from A taxonomic monograph of the leaf-litter inhabiting weevil genus Plumolepilius new genus (Coleoptera: Curculionidae: Molytinae: Conotrachelini) from Mexico, Guatemala, and El Salvador. 25713 records from Museu Paraense Emílio Goeldi - Diptera Collection. 3963 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 183617 records from LACM Entomology Collection. 22146 records from Bryophyte herbarium, Tromsø Museum. 41 records from Revisión periódica de Agave victoriae-reginae en el apéndice II de la CITES. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 40 records from Ecología evolutiva de dos especies invasoras de humedales en la República Mexicana: Arundo donax y Phragmites australis (Poaceae). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 35 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 158 records from The genus Anisoscelis Latreille (Hemiptera: Heteroptera: Coreidae: Coreinae: Anisoscelini): new species, taxonomical arrangements, distributional records and key. 27 records from New records in vascular plants alien to Kyrgyzstan. 1157 records from Fitoplancton marino frente a Baja California. 1. Bahía de Todos Santos, BC. 13597 records from Orthopteroidea. 511 records from Coleoptera of Swierklaniec Forest. 450 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 12370 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 15637 records from CCBER Herpetology Collection. 53380 records from IAC - Herbário do Instituto Agronômico de Campinas. 9972 records from SANT-Lich. 367 records from QLD DERM Coastal Bird Atlas (Trial). 49 records from Nine new species of the genus Deinopteroloma Jansson, 1946 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from China and Vietnam. 230 records from A taxonomic revision of the Neotropical myrmicine ant genus Lachnomyrmex Wheeler (Hymenoptera: Formicidae). 16 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas III. Suctobelbella alloenasuta n. sp. und Suctobelbella messneri n. sp. sowie die bisher aus der DDR bekannten Arten der nasalis-subtrigona-Gruppe (Suctobelbidae). 7 records from Additions to the Genus Phyllodesmium, with a Phylogenetic Analysis and its Implications to the Evolution of Symbiosis. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 3 records from A new two-pored species of Amphisbaena (Squamata, Amphisbaenidae) from the Brazilian Cerrado, with a key to the two-pored species of Amphisbaena. 156 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 203 records from Variabilidad genética en las poblaciones naturales de la almeja catarina Argopecten ventricosus-circularis (Sowerby II, 1842). 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 561820 records from Bee Biology and Systematics Laboratory. 1 records from Egg capsules of Atlantoraja cyclophora (Regan, 1903) and A. platana (Günther, 1880) (Pisces, Elasmobranchii, Rajidae).. 1 records from Oribates calcaratus. 8 records from Order Diptera, family Mydidae. 504 records from Flora leñosa de la reserva La Selva El Ocote. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 4 records from A new Indian species of Pardoteleia Kozlov & Lê (Hymenoptera: Scelionidae: Scelioninae) and first description of the male. 8 records from Review of the Ulopella leafhopper genus group (Auchenorrhyncha, Cicadellidae, Ulopinae) with description of a new genus and species collected from pitfall traps in Zambia. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 359 records from Base de datos de las cicadas mexicanas. 56 records from Guide to the Parasites of Fishes of Canada Part V: Nematoda. 6801 records from UPRM Invertebrate Collection. 1305 records from Herpetofauna de las sierras La Candela, Jerez de García Salinas y El Mastrante. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 12 records from Revision of the genus Kailasha (Lepidoptera, Erebidae, Arctiinae) from Oriental region, with description of one new species. 2 records from Two New Jumping Spiders of the Genus Chalcoscirtus from China (Araneae: Salticidae). 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 1 records from Miriapodi di alcune grotte della Campania. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 6639 records from Laptev Sea and Nansen Basin Zooplankton, 1993. 9 records from Four new species of Lorryia (Acari: Tydeidae) associated with Hevea brasiliensis Muell. Arg. (Euphorbiaceae) in Brazil. 57220 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 3 records from A new Paramathes Boursin, 1954 (Lepidoptera, Noctuidae) species from China. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 120 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 1284 records from Collection of Heteroptera. 1 records from Cepolacanthus kimi, a new genus and species of copepod (Cyclopoida: Taeniacanthidae) parasitic on Bandfish Acanthocepola abbreviata (Valenciennes, 1835) (Actinopterygii: Cepolidae) caught off the Iraqi coast. 3 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 11803 records from Computarización de la Colección Nacional de Crustáceos del Instituto de Biología, UNAM y elaboración de su catálogo. 100 records from Review of the genus Siemssenius Weise, 1922 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 122 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 151 records from Hidden diversity in deep-water bandfishes: review of Owstonia with descriptions of twenty-one new species (Teleostei: Cepolidae: Owstoniinae). 3 records from Study of the Oriental genus Alishania Vilbaste (Hemiptera: Cicadellidae: Deltocephalinae) from China with description of one new species. 2533 records from Inventario florístico de Tetipac y sus alrededores (Sierra de Taxco). 2 records from A new phreatic catfish of the genus Phreatobius Goeldi 1905 from groundwaters of the Itenez River, Bolivia (Siluriformes: Heptapteridae).. 555 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 86 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 35325 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 121230 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 24 records from New species of Thelepodidae (Terebelliformia, Polychaeta) from Taiwan. 4579 records from Herbarium WRSL, Flora of the Silesia. 829 records from Colección Hidrobiológica del Chocó. 575618 records from AntWeb. 84072 records from Actualización de la Colección de Artrópodos con importancia médica (CAIM), Laboratorio de Entomología, InDRE. 17 records from A new species and new records of the genus Neotarsonemoides Kaliszewski, 1984 (Acari: Tarsonemidae) from East Azerbaijan province, Northwestern Iran. 67 records from Australian mycophagous species of the genus Deplorothrips (Thysanoptera, Phlaeothripinae). 3 records from A Partial Revision of the Genus Metabelba Grandjean (Oribatei, Acarina). 36 records from Retrocitomyia Lopes, 1982 (Diptera: Sarcophagidae): new species, new records, key to males, and an updated catalog. 3462 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from New sighting of the endangered species blackchin guitarfish, Rhinobatos cemiculus, in the South Aegean Sea. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 11 records from The larvae of Hydropsyche rhadamanthys Malicky 2001 and Hydropsyche sarpedon Malicky 2001 (Trichoptera: Hydropsychidae), endemics of Crete (South Aegean, Greece), with notes on their ecology. 3 records from A millipede missing link: Dobrodesmidae, a remarkable new polydesmidan millipede family from Brazil with supernumerary rings (Diplopoda, Polydesmida), and the establishment of a new suborder Dobrodesmidea. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 5 records from New genus and species of ant-like true bug (Hemiptera: Miridae) from the Canary Islands. 16 records from New records of doryctine wasps (Hymenoptera: Braconidae) from Argentina, with the description of Shawius diiorioi Martínez sp. nov.. 1 records from Ankerius aenigmaticus, a new genus and new species of aphanodactylid crab symbiotic with polychaetes from the Red Sea coast of Saudi Arabia (Crustacea: Decapoda: Brachyura: Aphanodactylidae). 26 records from Description of a new cyprinid species, Labeo meroensis n. sp. (Teleostei: Cyprinidae), from the River Nile.. 4050 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 177466 records from CAS Entomology (ENT). 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 2 records from Record of a new species of the genus Viridopromontorius Luna de Carvalho (Strepsiptera: Corioxenidae) from India with a revised key to Corioxenidae. 2116 records from Collection entomologique Pierre Lachiver. 3 records from Dinosaurs from the Cretaceous of South China. 810 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 4993 records from Otter in coastal areas - Carcasses. 64 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 2 records from Papakula and Hesydrimorpha: how two spider genera were described from the same species collected from the same locality (Araneae: Pisauridae). 3 records from A distinctive new species of gnatcatcher in the Polioptila guianensis complex (Aves, Polioptilidae) from western Amazonian Brazil. 259949 records from Zoology (Museum of Evolution - Uppsala). 1 records from Lissotes working-group. 4847458 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 1 records from Oribates fuscipes. 9 records from A new species of Monstrilla Dana, 1849 (Copepoda: Monstrilloida: Monstrillidae) from Korea, including a key to species from the north-west Pacific. 62 records from The North American spider genera Paratheridula, Tekellina, Pholcomma and Archerius (Araneae: Theridiidae). 536 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 2421 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 100 records from Brock University Herbarium (BU). 1196 records from Entomological collection of the National Museum. 1 records from The larva and prepupa of Eupareophora exarmata (Thomson, 1871) (Hymenoptera, Tenthredinidae). 1 records from Zetes cespitum. 13253 records from CHAS Ornithology. 26397 records from Herbarium Senckenbergianum (GLM) - Lichenes. 22804 records from Biodiversity Research and Teaching Collections - TCWC Marine Invertebrates. 36 records from First Inventory of Sea Anemones (Cnidaria: Actiniaria) of the Mexican Caribbean. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 122 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 48803 records from SPSF - Herbário Dom Bento José Pickel. 7 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 76 records from A new species of Fidelia Friese, 1899 (Hymenoptera, Megachilidae), with a key to the species of the genus. 2562 records from Inventario de la vegetación acuática vascular de cuatro regiones hidrológicas prioritarias del centro de México. 852 records from Estructura poblacional, variación genética y conservación de tres especies del género Pinus, endémicas de México. 9077 records from Actualización y adiciones a la Colección de Poliquetos del Instituto de Ciencias del Mar y Limnología, UNAM. 6 records from Coleção de Tardigrada do Museu Nacional - UFRJ. 2 records from Out of the Neotropics: newly discovered relictual species sheds light on the biogeographical history of spider ants (Leptomyrmex, Dolichoderinae, Formicidae). 1 records from Nothrus segnis. 1 records from Hoplophora ferruginea. 63415 records from MMNS Ichthyology Collection. 499 records from Seasonal dynamics of sub-ice fauna below pack ice in the Arctic (Fram Strait). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 29865 records from SANT-Algae. 6237 records from Plecoptera. 145017 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 8 records from Cave species of the genus Anurida (Collembola: Neanuridae) from Korea, with the description of new species. 361 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 9 records from On the generic placement and taxonomic status of some Miltochrista taxa described by Franz Daniel (Lepidoptera, Erebidae, Arctiinae). 10 records from Description of a new species of the Afrotropical spider genus Afroneutria (Araneae, Ctenidae). 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 23484 records from ZUEC-AMP - Coleção de Anfíbios do Museu de Zoologia da UNICAMP. 130 records from Endemic earthworms (Oligochaeta: Lumbricidae) of the Balkan Peninsula: a review. 1124142 records from PRECIS. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 4464 records from Passalidae y Lucanidae (Coleoptera: Scarabaeoidae) de México. 1866 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 8 records from Colección de Referencia de Urocordados del Museo de Ciencias de la Universidad El Bosque. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 2 records from Scaphisoma poussereaui sp. nov. from La Réunion (Coleoptera: Staphylinidae: Scaphidiinae), arange extension of the S. tricolor species group. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 41090 records from CSIRO Ichthyology provider for OZCAM. 239 records from Systematic review of the neotropical shovelnose catfish genus Sorubim Cuvier (Siluriformes: Pimelodidae).. 1 records from A New Genus and Species of Blind Sleeper (Teleostei: Eleotridae) from Oaxaca, Mexico: First Obligate Cave Gobiiform in the Western Hemisphere. 370865 records from Herbario Nacional Colombiano (COL). 1 records from Celaeno obsoleta. 58 records from New species and synonymies in Xenopygus Bernhauer (Coleoptera: Staphylinidae: Staphylinini). 1 records from Spongillaflies (Neuroptera, Sisyridae) in Baltic amber. 13094 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 283 records from HSU Vertebrate Museum Birds Collection. 341 records from Evaluación bioecológica y ambiental de las áreas arrecifales del Caribe colombiano. 7 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 1201 records from Monocotyledonous Geophytes of Fergana Valley. 1678 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 459150 records from Fishbase. 6 records from A new genus of freshwater crab of the tribe Kingsleyini Bott, 1970 (Crustacea: Decapoda: Brachyura: Pseudothelphusidae) with description of a new species from Mato Grosso, Brazil. 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 22 records from Colección Parasitológica del Centro Nacional Patagónico (CNP-PAR). 3539 records from Naturalis Biodiversity Center (NL) - Pisces. 29 records from Opistognathus ensiferus, a new species of jawfish (Opistognathidae) from the Gulf of Mannar, India, with redescription of O. solorensis Bleeker. 5 records from Pseudonemesia tabiskey, a new species of Pseudonemesia Caporiacco 1955 and new ultramorphological data for the Microstigmatinae (Araneae: Microstigmatidae). 1 records from Oribates gilvipes. 9 records from Australian freshwater sponges with a new species of Pectispongilla (Porifera: Demospongiae: Spongillida). 39 records from Inventario de especies de vertebrados para apoyar la creación del Ordenamiento Ecológico y la Reserva de la Biósfera Janos, Chihuahua. 1854 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 6 records from Histoire naturelle des Hymenopteres. Deuxieme partie: Les Formicides.. 3 records from An annotated checklist of the psyllids of New Zealand (Hemiptera: Psylloidea). 6 records from Description of two new species of the catfish genus Trichomycterus from southeastern Brazil (Siluriformes: Trichomycteridae).. 14590 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 7 records from Description of two new species of Seinura Fuchs, 1931 (Nematoda: Aphelenchoididae) from Iran. 5600 records from Flora del municipio de Culiacán, Sinaloa. 19 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 5506 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 99 records from Ecología de comunidades microbianas en las aguas subterráneas de Cuatrociénegas, Coahuila. 2270 records from UTEP Plants (Arctos). 119093 records from Occurrence records of southern African aquatic biodiversity. 7693 records from NHM, Heteroptera. 1 records from A new species of the genus Rhinoecetes Just, 1983 (Crustacea: Amphipoda: Ischyroceridae) from Japan. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 2 records from Re-description of the Arctic tardigrade Tenuibiotus voronkovi (Tumanov, 2007) (Eutardigrada; Macrobiotidea), with the first molecular data for the genus. 11 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 3 records from First record of the thread-legged assassin bug genus Proguithera from Japan, with description of a new species (Hemiptera: Heteroptera: Reduviidae). 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 555 records from Review of Dissomphalus Ashmead, 1893 (Hymenoptera, Bethylidae) from Espíri- to Santo, Brazil, with description of twenty-one new species. 18 records from Nivalios gen. nov. (Hemiptera: Fulgoromorpha: Flatidae), first record of the tribe Nephesini from China. 16 records from Taxonomic review of the genus Wasmannia.. 2 records from A new species of Prohatschekia Nunes-Ruivo, 1954 (Siphonostomatoida: Hatschekiidae) from the scorpaenid fish, Scorpaena neglecta Temminck & Schlegel, 1843 (Scorpaeniformes: Scorpaenidae), in Korean waters. 463 records from Sistemática molecular y poblacional de especies del género Chirostoma (Pisces: Atherinidae). 6086 records from Computarización de las colectas del estado de Morelos depositadas en el Herbario HUMO de la Universidad Autónoma del Estado de Morelos. 25 records from Metrocoris Mayr (Insecta: Hemiptera: Gerridae) of India with descriptions of five new species. 12 records from New species of Rhorus Förster, 1869 (Hymenoptera: Ichneumonidae: Ctenopelmatinae) from South Korea. 70913 records from SPF - Herbário da Universidade de São Paulo. 17 records from The Neotropical tanyderid Araucoderus gloriosus (Alexander) (Diptera, Tanyderidae), with description of the egg, larva and pupa, redescription of adults, and notes on natural history. 40 records from Cerambycidae (Insecta: Coleoptera) of Quixadá, Ceará State, Brazil: new records and new species. 8 records from A new species of the genus Nothobranchius (Cyprinodontiformes: Nothobranchiidae) from the coastal area of northeastern Mozambique.. 70772 records from SANT Herbarium vascular plants collection. 7 records from Collection Myriapoda - SNSD. 782 records from Genética poblacional y filogeografía de las tortugas marinas golfina (Lepidochelys olivacea) y laúd (Dermochelys coriacea) en el Pacífico mexicano. 2731 records from Collection du Musée d'Histoire Naturelle de Nice. 5103 records from Elaboración del banco de datos de las colecciones del Museo de Zoología-CIQRO. 2 records from The Persian / Arabian Gulf's sole great white shark Carcharodon carcharias (Lamniformes: Lamnidae) record from Kuwait: misidentification of a sandtiger shark Carcharias taurus (Lamniformes: Odontaspididae).. 13403 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 6 records from Description of two new species from China in a new species group of the fig wasp genus Sycophaga Westwood (Hymenoptera: Chalcidoidea: Agaonidae: Sycophaginae). 1 records from A Late Cretaceous diversification of Asian oviraptorid dinosaurs: evidence from a new species. 2 records from Begonia jaguarensis L. Kollmann, R. S. Lopes & Peixoto (Begoniaceae), a new species from North of Espírito Santo State, Brazil. 2 records from Beiträge zur Kenntnis bulgarischen Chilopoden. Teil V. Das Genus Polybothrus. 1 records from Miriapodi di alcune grotte della Campania. 20 records from A mountain of millipedes IV: Species of Prionopetalum Attems, 1909, from the Udzungwa Mountains, Tanzania. With notes on “ P. ” fasciatum (Attems, 1896) and a revised species key (Diplopoda, Spirostreptida, Odontopygidae). 3535 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 16 records from Endemism and long distance dispersal in the waterfleas of Easter Island. 384 records from New genera, species and records of Maeridae from Australian Waters: Austromaera, Ceradocus, Glossomaera, Hamimaera, Huonella gen. nov., Linguimaera and Maeraceterus gen. nov. (Crustacea: Amphipoda). 167515 records from KUBI Mammalogy Collection. 4 records from Lepidoptera (Observations). 8 records from New species of the catfish genus Trichomycterus (Siluriformes, Trichomycteridae) from the headwaters of the rio São Francisco basin, Brazil.. 10577 records from Biological Reference Collections ICM CSIC. 5227 records from Las familias Polyporaceae sensu stricto y Albatrellaceae en México. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 8 records from Pomacentrus aurifrons, a new species of damselfish (Pomacentridae) from Melanesia.. 1 records from new species of the fungus-farming ant genus Mycetagroicus Brandao & Mayhe-Nunes A new species of the fungus-farming ant genus Mycetagroicus Brandao Mayhe-Nunes (Hymenoptera, Formicidae, Attini).. 2 records from Apistogramma eremnopyge, a new species of cichlid fish (Teleostei: Cichlidae) from Peru.. 372 records from Colección de Entomología - Arthropoda. 1165 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 24 records from Review of the genus Defilippia Lioy (Bombyliidae, Diptera) from Egypt, with description of a new species, new combinations, and a neotype designation for D. pharaonis (Paramonov, 1928). 49983 records from UFP - Herbário UFP - Geraldo Mariz. 702 records from HSU Vertebrate Museum Reptile Collection. 3447 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 444 records from Insect Collection from New Caledonia. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Hoehlen. 127 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 19 records from New tribe Labiobaetini tribus n., redefinition of Pseudopannota Waltz & McCafferty 1987 and descriptions of new and little known species from Zambia and Uganda. 3182 records from Finnish Entomological Database: Heteroptera. 544 records from Naturalis Biodiversity Center (NL) - Foraminifera. 7509 records from Perot Museum of Nature and Science. 12 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 9216 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_NL. 1706 records from University of Amsterdam (NL) - Páramo pollen reference collection. 558 records from Mammals in MZNA-VERT: skull and teeth development in Rattus and Mus. 8399 records from Evaluación del estado de conservación de las poblaciones de Passerina ciris, P. leclancherii, P. amoena, P. rositae, P. caerulea, Cardinalis cardinalis y C. sinuatus en México: recomendaciones para su conservación y aprovechamiento sustentable. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 41984 records from Repatriación de datos de los lepidópteros depositados en la Colección del McGuire Center for Lepidoptera and Biodiversity, Florida Museum of Natural History. 23 records from New and interesting species of the genus Bryaxis Kugelann, 1794 (Coleoptera, Staphylinidae, Pselaphinae) from Croatia. 77 records from Empria and Monsoma in Japan. 38 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 19100 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 654 records from Helgeland Museum, Tabanidae. 52 records from New data on the jumping spiders of the subfamily Spartaeinae (Araneae: Salticidae) from Africa. 107360 records from Colección Herbario Federico Medem Bogotá - FMB. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from Three new species of Claudiella Reichardt & Vanin, 1976 (Coleoptera, Torridincolidae) from Brazil. 2519 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 891 records from Taxonomía de los pinos del noreste de México. 2 records from A new skate genus Orbiraja (Rajiformes: Rajidae) from the Indo-West Pacific. 4849 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 11 records from Allopatric color forms of Scaphidium morimotoi Löbl, 1982 (Coleoptera, Staphylinidae, Scaphidiinae) endemic to the Amami Islands, the Ryukyus, Japan. 2 records from Epidaus wangi (Hemiptera: Heteroptera: Reduviidae), a new assassin bug from Tibet, China. 235 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 10 records from A new wobbegong shark, Orectolobus hutchinsi n. sp. (Orectolobiformes: Orectolobidae) from southwestern Australia.. 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 47499 records from Sphaeroceridae Collection. 18055 records from Cercle des mycologues de Montréal Fungarium (CMMF). 3578 records from MBML-Mamiferos - Coleção de Mamíferos. 197931 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 21 records from On the genus Elasmopus Costa, 1853 from the Northeastern Coast of Brazil with five new species and new records. 1415 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 2465 records from Macroalgas marinas de la Región de Zihuatanejo, Gro.. 318 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 19 records from Conocimiento y conservación de las mamilarias endémicas del Valle de Tehuacán-Cuicatlán. 1329 records from API_CRSN_Data. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 7671 records from HERBAM - Herbário da Amazônia Meridional. 2 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 26835 records from Herbario Pontificia Universidad Javeriana. 16 records from A new species of Mesovelia (Heteroptera: Gerromorpha: Mesoveliidae) from South America, with identification key and notes on Colombian species. 2174 records from MLZ Mammal Collection (Arctos). 123682 records from ICN - Herbário do Instituto de Ciências Naturais. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 14 records from A new subterranean Iberian Cephennium with unusually modified metatrochanters (Coleoptera, Staphylinidae, Scydmaeninae). 9 records from Contributions to the knowledge of the biodiversity of Heteroptera (Insecta) in the Southern Cone, Argentina. 50317 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 4778 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 1 records from The first described male Tube-web Spider for mainland Australia: Ariadna kiwirrkurra sp. nov. (Araneae: Segestriidae). 4490 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 26 records from A new species of Chondrostoma Agassiz, 1832 (Cypriniformes: Cyprinidae) with sexual dimorphism from the lower Rio Tejo Basin, Portugal.. 68838 records from IICT Herbário LISC. 85003 records from Herbario Universidad de Antioquia (HUA). 2 records from Note sur les fourmis du Musée Zoologique de l'Académie Impériale des Sciences à St. Pétersbourg.. 159783 records from Lund Museum of Zoology - Insect collections (MZLU). 99 records from Observations on the biology of Afrotropical Hesperiidae (Lepidoptera) with particular reference to Kenya. Part 10. Pyrginae, Carcharodini. 1 records from A new species of the genus Tetratoma Fabricius (Coleoptera, Tetratomidae) from China. 1995 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 44 records from Diversity of Scydmaeninae (Coleoptera: Staphylinidae) in Upper Eocene Rovno amber. 89699 records from URM - Herbário Pe. Camille Torrand. 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 3 records from A new species of the genus Meganola Dyar, 1898 (Lepidoptera, Nolidae, Nolinae) from China. 1 records from On centipedes (Chilopoda) of Albania, 2. 84054 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 1 records from Nothrus biciliatus. 3 records from Note su alcune specie di chilopodi della regione palestinese. 1 records from Myriopoden von Kreta, nebst Bitraegen zur allgemeinen Kenntnis einger Gattungen. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 346643 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 4501 records from Colección de Mamíferos del Centro Nacional Patagónico. 1 records from Hoplophora decumana. 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 597 records from Collection Crustacea - KAUMM. 2113 records from Flora ficológica de la huasteca potosina. 88 records from Revision of the genera Pareuthria Strebel, 1905, Glypteuthria Strebel, 1905 and Meteuthria Thiele, 1912 (Gastropoda: Buccinulidae) with the description of three new genera and two new species from Southwestern Atlantic waters. 8 records from Five new feather mites of the subfamily Pterodectinae (Acariformes: Astigmata: Proctophyllodidae) from passerines and hummingbirds (Aves) of Brazil. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 13 records from Two new species of Neocorynura from Guatemala (Hymenoptera: Halictidae: Augochlorini) with a key to the species known from the country. 44 records from Solanum_baretiae. 3643 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 1521 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 275 records from Inventario de la fauna arrecifal asociada al ecosistema de Pocillopora en el Pacífico Tropical Mexicano. 38 records from Revision of the Rhinophoridae (Diptera: Calyptratae) of Japan. 6 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 9 records from Eusyllinae, Exogoninae and Autolytinae (Syllidae: Polychaeta) from the Southern Mexican Pacific, with the description of three new species. 3 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 2 records from A new diminutive sisorid catfish (Actinopterygii: Siluriformes) from northeastern India. 1 records from Oribates flammula. 4 records from A new species of the genus Anthalona Van Damme, Sinev & Dumont, 2011 (Cladocera: Anomopoda: Chydoridae) from North-East Thailand. 4 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 1 records from Eremaeus hepaticus. 6817 records from Colección de Reptiles del Instituto Alexander von Humboldt. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 10065 records from Malezas introducidas en México. 61981 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 5444 records from Herpetology. 3000 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 27 records from Review of the plant bug genus Fingulus Distant in Indochina (Hemiptera: Heteroptera: Miridae: Deraeocorini), with descriptions of two new species. 167 records from Código de barras de diferentes grupos de peces mexicanos endémicos de la Mesa Central Mexicana. 146 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 8936 records from A Distribution and Taxonomic Reference Dataset of Geranium (Geraniaceae) in the New World. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 798 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Cepheus latus. 417946 records from Entomology, Natural History Museum, University of Oslo. 391 records from Demografía e historia de vida de la lagartija Xenosaurus newmanorum en Xilitla, San Luis Potosí. 4 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 27 records from Sistemática molecular de Trogoniformes (Aves): Filogenia del orden y análisis de variabilidad genética de quetzales en la reserva de la Biosfera El Triunfo. 663 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 253104 records from Lyman Entomological Museum (LEMQ). 1 records from Pelops torulosus. 956 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 173415 records from Hymenoptera specimen database of Kyushu University. 6855 records from Echinoderm collection of National Museum of Nature and Science. 1 records from Oribates picipes. 35901 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 1 records from Arthropoden aus südostalpinen Höhlen.. 1 records from Dolistenus menozzii n. sp. della famiglia Platydesmidae (Miriapodi Colobognati); e altri miriapodi della Calabria. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 13086 records from Collection of Coleoptera. 381 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 5 records from A new species of Australian frog (Myobatrachidae: Uperoleia) from the New South Wales mid-north coast sandplains. 24945 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 204 records from Hosted Invertebrate Collection 01. 1489 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 950 records from Fishes in MZNA-VERT: freshwater fishes of Hidalgo state (Mexico). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 41 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 585 records from Ascomycetes of Russian Fennoscandia. 17 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 4854 records from Inventario de las especies de hongos microscópicos en el Valle de Zapotitlán, estado de Puebla. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 6 records from Two new planthopper species (Hemiptera, Fulgoroidea, Caliscelidae) collected in pitfall traps in Zambia. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 5 records from Two new species of Diastatotropis Lacordaire (Coleoptera: Anthribidae) from east Madagascar with a key to species of the genus. 506 records from Nemátodos acuáticos de vida libre de Quintana Roo. 3 records from A new species of the genus Leptobrachium (Anura: Megophryidae) from the Gaoligongshan Mountain Range, China. 1163 records from Detección de reclutas de la dorada Sparus aurata como medida del nivel de establecimiento en la Bahía de La Paz, BCS. 5850 records from UAFMC Fish. 26 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 1 records from Taenioides kentalleni, a new species of eel goby from Saudi Arabia (Gobiidae: Amblyopinae).. 71 records from Colección de Referencia de Peces del Museo de Ciencias de la Universidad El Bosque. 8721 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 152904 records from SA Flora (BDBSA). 77 records from Xiphosura collection of National Museum of Nature and Science. 80128 records from NCSM Fishes Collection. 9173 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 365 records from Colección Herpetológica de la Patagonia. 918 records from Western Australia Museum, Crustacea Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1920-2004. 2 records from A new genus and new species of subfamily Trioxinae (Hymenoptera: Aphidiidae) from the Far East of Russia. 11 records from New records and a new species of bivalve (Mollusca: Bivalvia) from Miocene hydrocarbon seep deposits, North Island, New Zealand. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 453 records from Avifauna del Altiplano de San Luis Potosí. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 57 records from Eight new species of MacvIcarIa Gibson and Bray, 1982 (Digenea: Opecoelidae) mainly from endemic temperate marine fishes of Australia. 84 records from Colección de Referencia de Equinodermos del Museo de Ciencias de la Universidad El Bosque. 5 records from On Jungicephus Maa (Hymenoptera: Cephidae) with description of a new species from China. 403 records from Revision of Afrotropical Dyscritobaeus Perkins, 1910 (Hymenoptera: Scelionidae). 29 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 46432 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 4266 records from UAFMC Birds. 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 2457 records from Ontario BioBlitz Species Records. 1 records from A new Garcorops species from Madagascar copal (Araneae: Selenopidae). 1 records from Erysipelothrix inopinata sp. nov., isolated in the course of sterile filtration of vegetable peptone broth, and description of Erysipelotrichaceae fam. nov.. 3 records from Unraveling a new lineage of Hydrobiidae genera (Caenogastropoda: Truncatelloidea) from the Ponto-Caspian region. 20 records from A review of the genus Eotmethis (Orthoptera, Acridoidea, Pamphagidae) with two new species and key to known species of the genus from China. 19743 records from Avifauna de la Reserva de la Mariposa Monarca. 36 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 138919 records from AM: Freshwater Invertebrates (1900-2005). 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 11616 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 26 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 303 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 67236 records from Depuración de la colección y base de datos del Herbario CICY. Fase IV. 71 records from Estudios previos justificativos para la declaratoria de áreas naturales protegidas en Tamaulipas. 2859 records from Coleoptera, NEF. 61129 records from Base de datos de mamíferos de México depositados en colecciones de Estados Unidos y Canadá. 2 records from A new Pararistolochia Hutch. & Dalziel (Aristolochiaceae) from the Beanka Tsingy (western Madagascar). 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 9 records from Urogymnus acanthobothrium sp. nov., a new euryhaline whipray (Myliobatiformes: Dasyatidae) from Australia and Papua New Guinea. 347 records from Peces, ictioplancton y helmintos parásitos en la Bahía de Chetumal (Santuario del Manatí). 4761 records from SMDB - Santa Maria Departamento de Biologia. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 12 records from New Leucettidae de Laubenfels, 1936 (Porifera, Calcarea) from Western Australia. 23 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 471 records from Aschelminth collection of National Museum of Nature and Science. 108163 records from BioFokus. 27890 records from Amphibian Specimens. 225385 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 4498 records from Colección Herbario Universidad Católica de Oriente. 128 records from Coleção de Nematoda do Museu Nacional - UFRJ. 7187 records from Estudio florístico, ecológico y etnobotánico, en el área natural protegida "Tenancingo-Malinalco-Zumpahuacan", Estado de México. 2 records from Note tassonomiche e faunistiche su Chilopodi della Grecia (Chilopoda). 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 10 records from Plateurytion roigi sp. nov., a new geophilid centipede (Myriapoda: Chilopoda: Geophilomorpha) from Southern Chile. 52 records from The Myrmica punctiventris and M. crassirugis species groups in the Nearctic region.. 2 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 5 records from Revision of the coral-inhabiting genus Conopea (Cirripedia: Archaeobalanidae) with description of two new species of the genera Conopea and Acasta. 792 records from The Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 161 records from Orthoptera (Insecta: Tettigonioidea, Pyrgomorphoidea, Acridoidea) of Kafa Biosphere Reserve, Bale Mountains National Park and other areas of conservation interest in Ethiopia. 162 records from Estimación de biomasa de abulón Haliotis spp. en la zona de Bahía Tortugas, BCS. 10034 records from UAM Fish Collection (Arctos). 27 records from First occurrence of Nemobiinae crickets in the Lesser Antilles (Orthoptera, Grylloidea, Trigonidiidae), with the descriptions of three new species. 47357 records from DMNS Bird Collection (Arctos). 766 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 2 records from Arthropoden aus südostalpinen Höhlen.. 2 records from n the type species of the genus Aetius O. Pickard-Cambridge, 1896: The first description of male with notes on cymbial notch and mating plug (Araneae: Corinnidae: Castianeirinae). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 6217 records from Museu Paraense Emilio Goeldi - Coleoptera Collection. 3945 records from TTRS Ornithology. 15572 records from The Fish Collection at the Zoologische Staatssammlung München. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 1 records from Zetes rubens. 312 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 127876 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 1 records from Nothrus pollinosus. 2 records from A new cave-dwelling species of the genus Mesoiulus Berlese, 1886 (Diplopoda, Julida, Julidae) from Turkey. 12051 records from ISM Ornithology Collection. 23 records from Two new species of Pseudolaguvia (Teleostei: Erethistidae) from Bangladesh.. 7 records from Description of Eutetrapha weni n. sp. from Guizhou, China (Coleoptera: Cerambycidae: Lamiinae: Saperdini). 3 records from One new species of the subgenus Xizicus (Zangxizicus) (Orthoptera: Tettigoniidae: Meconematinae) from China. 12 records from The genus Dromanthomorphus Pic, 1921 (Coleoptera, Cleroidea: Malachiidae) in South-East Asia. 23115 records from Naturalis Biodiversity Center (NL) - Odonata. 15 records from A new species of Cynopotamus Valenciennes, 1849 (Characiformes, Characidae) with a key to the species of the genus.. 46 records from Coleção de Nematomorpha do Museu Nacional - UFRJ. 75677 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 255 records from GENT Lactarius Deliciosi. 1421 records from Algas coralinas articuladas (Rhodophyta-corallinales) de México. 148 records from BioAcoustica: Wildlife Sounds Database. 1 records from Myriopoden von Epirus. 8 records from A new species of Moenkhausia Eigenmann, 1903 (Characiformes: Characidae) from Amazon basin, Brazil. 4 records from A new species of the genus Paramesotriton (Caudata: Salamandridae) from Fujian, southeastern China. 102 records from Sipuncula collection of National Museum of Nature and Science. 46 records from Three new Sisyphus species (Coleoptera: Scarabaeidae: Scarabaeinae) from shaded vegetation in southern Africa. 6584 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 1049 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 11 records from Germalus species of the Malagasy region (Heteroptera: Lygaeoidea: Geocoridae). 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 59 records from Further studies on south eastern Asian Luciolinae: 1. Sclerotia Ballantyne, a new genus of fireflies with back swimming larvae 2. Triangulara Pimpasalee, a new genus from Thailand (Coleoptera: Lampyridae). 12 records from The taxonomic status and sister group relationship of the cardinalfish species Jaydia striatodes (Percomorphaceae: Apogonidae). 156 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 2654 records from Collection of Hymenoptera. 1 records from On the genus Sunius Curtis, 1829 of Turkey. IV. A new micropterous species from southwestern Anatolia and additional records (Coleoptera: Staphylinidae: Paederinae). 1 records from Miriapodi di alcune grotte della Campania. 374 records from Diversidad y distribución del género Tripsacum (Poaceae: Tripsacinae) en México. 3105 records from Coleção de Echinodermata do Museu Nacional - MNRJ-ECHINO. 125 records from Danish Lacewings (Neuroptera). 1 records from Nothrus pigerrimus. 102 records from Macroalgas marinas de Baja California Sur Parte I: Bahía de la Paz y Bahía de la Ventana. 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 1 records from Physoschistura walongensis, a new species of loach (Teleostei: Nemacheilidae) from Arunachal Pradesh, northeastern India. 12005 records from Inventario florístico de la familia Boraginaceae en México. Fase II. 156 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from Taxonomic considerations on Lobocneme Rehn, 1911 and Paroxyopsis Rehn, 1911 and a new synonymy (Insecta Mantodea: Stagmatopterinae). 8739 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 54420 records from CESJ - Herbário Leopoldo Krieger. 1 records from On the occurrence of caligids (Copepoda: Siphonostomatoida) in the marine plankton: a review and checklist. 13717 records from OUPR - Herbário "Professor José Badini". 45 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 8 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 50 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 6 records from Hedotettix angulatus sp. nov. (Orthoptera: Tetrigoidea: Tetrigidae, Tetriginae) a new pygmy grasshopper species from India. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 192948 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 892 records from Base de datos de la familia Fagaceae en el estado de Hidalgo. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 2396 records from The Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 34 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 155 records from Megophthalmidia_of_North_America. 244 records from Revision of Ogdoecosta Spaeth 1909 with description of Ogdoecosta paraflavomaculata López-Pérez, sp. nov. (Coleoptera: Chrysomelidae: Cassidinae: Mesomphaliini). 25830 records from Diatomeas (Bacillariophyceae) y Dinoflageladas (Dinophyceae) planctónicas más frecuentes en la región sur del Golfo de México. 13 records from First Amazonian species of Maracaynatum, with comments on the genus (Opiliones: Laniatores: Samoidae). 185359 records from NINA insect database. 4 records from A new species of Chirothripoides (Thysanoptera: Tubulifera) from India and Malaysia. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 2 records from Two new species of Mexican Rhinotragini and transference of Odontocera josemartii Zayas, 1956 to Stenopseustes (Coleoptera, Cerambycidae). 90 records from Apteronotus eschmeyeri, a new species of ghost knifefish from the Magdalena Basin, Colombia (Gymnotiformes: Apteronotidae).. 14520 records from El banco de datos del Herbario HCIB en línea (Fase I): Implementación del Sistema Biótica. 13116 records from HAS-Algae - Coleção Ficológica do HAS. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 77 records from Plantas alimenticias incluidas en la dieta local en el municipio de Montería, Córdoba. 1 records from Zetes ephippiatus. 11 records from Three new species and redescription of the type species of Soesilarishius Makhan, 2007 (Araneae: Salticidae: Euophryini). 34237 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 6103 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 2 records from Études myrmécologiques en 1886.. 5428 records from Inventario florístico y base de datos de la familia Cucurbitaceae en México. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 7410 records from Helgeland Museum, Lepidoptera. 15879 records from HAMAB - Herbário Amapaense. 1 records from Zetes fuscomaculatus. 2 records from A new species of Pelecium Kirby (Coleoptera: Carabidae: Peleciini) from the Atlantic Forest biome, Brazil. 22041 records from CUMV Mammal Collection (Arctos). 54 records from Molluscan fauna of Gueishan Island of Taiwan. 1 records from CIM Specimens. 10 records from A new burrowing crayfish of the genus Fallicambarus Hobbs, 1969 (Decapoda: Cambaridae) from the Red River Drainage of the southcentral United States. 14 records from New species and new synonyms in European Platypalpus (Diptera: Hybotidae). 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1952 records from ISM Ichthyology Collection. 8366 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 1 records from Notes on Cataglyphis Foerster, 1850 of the bicolor species-group in Israel, with description of a new species (Hymenoptera: Formicidae). 90894 records from CUMV Fish Collection (Arctos). 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 1782 records from Peces y Mamíferos de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua. 21 records from On the Lathrobium fauna of the Luoxiao Mountains, Central China. 23 records from A taxonomic revision of the kalshoveni species-group of the genus Nemophora Hoffmannsegg (Lepidoptera, Adelidae), with descriptions of six new species from Indonesia and Papua New Guinea. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 6065 records from LISU Herbario Angola. 3953 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 6 records from Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon.. 496530 records from Field Museum of Natural History (Zoology) Bird Collection. 109 records from A taxonomic revision of the genus Oxyopomyrmex André, 1881 (Hymenoptera: Formicidae). 1 records from A new African Apiocera species (Apioceridae, Diptera). 79 records from Estructura genética poblacional de las especies de Tapaojitos (Aves Parulinae: Geothlypis) que ocurren en los humedales de México: Uno de los hábitats más amenazados de nuestro país. 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 1861 records from Banc de Germoplasma Vegetal de les Illes Balears-JBS. 9 records from New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines. 352692 records from Plantae of Costa Rica (INBio). 6321 records from La Colección de Poliquetos (Annelida: Polychaeta) de la Facultad de Ciencias Biológicas, Universidad Autónoma de Nuevo León. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 5167 records from Fauna carcinológica de México. Crustáceos estomatópodos y decápodos del Golfo de México. Río Bravo, Tamaulipas a Cabo Catoche, Q.Roo. 30818 records from Bases de datos del proyecto análisis de la riqueza y el endemismo de la flora de México, con fines de su conservación, usando grupos y métodos selectos. 29540 records from Mycology herbarium, Tromsø Museum. 2 records from Re-description of the Arctic tardigrade Tenuibiotus voronkovi (Tumanov, 2007) (Eutardigrada; Macrobiotidea), with the first molecular data for the genus. 23 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 2937 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 131929 records from UAM Mammal Collection (Arctos). 10984 records from IZIKO: Marine Invertebrate Collection (1900-2011). 2 records from Pseudowuiessa, a new genus of brachypterous Mezirinae (Hemiptera: Heteroptera: Aradidae) from China. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 3 records from A new species of Lyssomanes Hentz, 1845 from Brazil (Araneae: Salticidae). 2481 records from HSU Wildlife Eggs and Nests. 866 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 31 records from New species of Macunahyphes Dias, Salles & Molineri (Ephemeroptera: Leptohyphidae), with taxonomic notes. 620 records from Digitalización de la colección FITO-UBIPRO, de las enfermedades y sus agentes causales, de los cultivos agrícolas de la región centro de México. 250 records from Indice de integridad biótica para comunidades de peces de la región alta del Río Pánuco. 2 records from A second species, and first Central American record, of the phorid fly genus Lenkoa Borgmeier (Diptera: Phoridae). 158 records from Biodiversidad del Phyllum Mollusca asociada a las plataformas de explotación de gas natural (Campo Chuchupa: La Guajira, Colombia). 301 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 10 records from A new family, genus and species of freshwater amphipod Australomicroprotopus megacoxa gen. nov. sp. nov. (Senticaudata, Corophiidea, Microprotopoidea, Australomicroprotopidae fam. nov.) from Australia. 8 records from A new pygmy grasshopper species (Tetrigidae: Tetriginae) from Central India. 1948 records from CCBER Mammalogy Collection. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 3 records from Key for identification of Cladocera of the subfamily Aloninae (Anomopoda: Chydoridae) from South-East Asia. 92 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 4 records from Duocrassana longula, new genus and species of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae) from southern Mexico and its relationship to other genera in Athysanini. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 9 records from Cypridinid Ostracods. 134 records from Propuesta de categorías de riesgo para la ictiofauna dulceacuícola de Oaxaca. 464 records from Lepidoptera systematic collection, NTNU University Museum. 100690 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 1826 records from Collection des Mollusques (BOUM). 31000 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 22 records from Two new paratanaid Tanaidacea (Crustacea: Malacostraca: Peracarida) from the Hawaiian Islands, with illustrated taxonomic keys. 1100 records from Proyecto de cultivo extensivo y comercialización de las mariposas de la región de Chajul, Chiapas. 13325 records from Herbier du Bénin. 4 records from Beiträge zur Kenntnis der Spinnenfauna des Kt. Tessin III - Für die Schweiz neue und bemerkenswerte Spinnen (Arachnida: Araneae). 15 records from Clasificación de tres especies endémicas de Mammillaria dentro del PROY-NOM-ECOL-059-2000. 2577 records from Shellfish (WSHN-MS). 82921 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 35 records from Flora of Słowiński National Park, Poland. 1 records from Systematics of the bubblegum corals (Cnidaria: Octocorallia: Paragorgiidae) with description of new species from New Zealand and the Eastern Pacific. 641 records from Fitoplancton marino frente a Baja California. 2. Áreas de surgencias de la región Ensenadense. 2444 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 804455 records from Museum Victoria provider for OZCAM. 3 records from A revision of the Neotropical spider genus Ancylometes Bertkau (Araneae: Pisauridae). 3769 records from Eggs Specimen. 127226 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 49827 records from CRCM Vertebrate Collection. 1275 records from Vertebrados terrestres de San Juan de Camarones, Durango. 8 records from New genus of diminutive microhylid frogs from Papua New Guinea. 17 records from New taxa and notes on some Landrevinae (Orthoptera: Gryllidae) from Malay Peninsula. 12681 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb).. 31 records from Further contribution to the knowledge of Georgian species of the Carabus Linnaeus, 1758 subgenus Neoplectes Reitter, 1885, with description of a new subspecies of C. titarenkoi Zamotajlov & Fominykh, 2014 (Coleoptera: Carabidae: Carabini). 45 records from A taxonomic review of Korean Liogluta Thomson (Coleoptera, Staphylinidae, Aleocharinae) with descriptions of three new species. 18940 records from Cowan Tetrapod Collection - Mammals. 13995 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 341 records from Inventario y monitoreo de anfibios y mariposas en la Reserva de Calakmul, Campeche. 1 records from Nouveautes sur la faune des Chilopodes de Yougoslavie. 2 records from A new species of Physomerus Burmeister (Hemiptera: Heteroptera: Coreidae: Coreinae), with a key to the species of India. 2 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 14502 records from Lepidoptera (Rhopalocera y Heterocera) de áreas prioritarias para la conservación en la Península de Yucatán, con registros de adultos y estados inmaduros. 6 records from Arthropoden aus südostalpinen Höhlen. 830 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 41001 records from Museu Paraense Emilio Goeldi - Mastozoology Collection. 276513 records from MBM - Herbário do Museu Botânico Municipal. 12184 records from Diversidad de abejas (Hymenoptera: Apoidea) de la Reserva de la Biosfera El Triunfo, Chiapas. 13625 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 12031 records from Flora de las playas y dunas costeras de México. 3 records from Odontotrypes (Odontotrupes) tawangensis new species (Coleoptera: Geotrupidae) from Arunachal Pradesh, India. 73 records from The "Martian" flora: new collections of vascular plants, lichens, fungi, algae, and cyanobacteria from the Mars Desert Research Station, Utah. 31 records from Coleção de Nemertea do Museu Nacional - UFRJ. 1387 records from Estudio de la diversidad florística de la región de Nizanda en el Istmo de Tehuantepec, Oaxaca. 2243 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase I (Tenango de Doria y Tlanchinol). 24 records from Description of the males of Euprosthenops australis Simon, 1898 and Euprosthenopsis pulchella (Pocock, 1902) (Araneae: Pisauridae). 3597 records from Harvestmen of French Guiana. 1322 records from PSUZC-Amphibians Collection. 2005 records from Abejas silvestres (Hymenoptera: Apoidea) de la región Praderas de Tokio-El Potosí - Sierra Mazmorras - Cañón de Iturbide, Coahuila y Nuevo León, México. 251732 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Nothrus canaliculatus. 2815 records from Helgeland Museum, Araneae. 6010 records from Computarización de la colección de insectos de la Universidad de Morelos, CIByC, UAEM. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 5 records from New species of Curculionichthys (Siluriformes: Loricariidae) from the eastern Guiana Shield. 8 records from New taxonomic, stratigraphic, and geographic information on the genus Faksephyllia Floris, 1972 (Scleractinia; Caryophylliidae); first records from the Oligocene of Austria, Germany, and Italy. 733 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 33 records from New records of snail-killing flies (diptera: Sciomyzidae) from Iran. 14 records from Estudio genético de las poblaciones de Rhizophora mangle en México. 4998 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 3 records from New Species of Woolly Lemur Avahi (Primates: Lemuriformes) in Bemaraha (Central Western Madagascar). 17571 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 3404 records from Lista florística de la Costa Grande del estado de Guerrero. 625 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 23 records from Revision of the generic classification of the hawkfishes (Cirrhitidae), with descriptions of three new genera.. 22 records from Five new species and a new country record in American Cerambycidae (Coleoptera). 157 records from Contribution to the knowledge of Chinese Phasmatodea III: Catalogue of the phasmids of Hainan Island, China, with descriptions of one new genus, one new species and two new subspecies and proposals of three new combinations. 63 records from Revision of the ant genus Myrmoteras in the Malay Archipelago (Hymenoptera, Formicidae).. 3276498 records from Insecta of Costa Rica (INBio). 17 records from Sarcinoid green algae (Chlorophyta) of Algal Collection of Soil Science Institute (ACSSI). 17 records from ZUEC-NMA - Coleção de Nematoda do Museu de Zoologia da UNICAMP. 18197 records from Atlas of Iberian water beetles (ESACIB database). 11392 records from Danish Plant Bugs (Miridae). 30999 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 1 records from Recharacterization of Rhinophis dorsimaculatus Deraniyagala, 1941 (Serpentes: Uropeltidae), including description of new material. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1495 records from Museu Paraense Emílio Goeldi - Mollusca Collection. 8951 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 67 records from Early-diverging bumblebees from across the roof of the world: the high-mountain subgenus Mendacibombus revised from species’ gene coalescents and morphology (Hymenoptera, Apidae). 43 records from Digital Florula - Las Cruces Biological Station. 2172 records from Colección de Reptiles. 24121 records from Endemic plants of the Congo basin. 32 records from Braconid wasps of subfamily Alysiinae (Hymenoptera: Braconidae) as endoparasitoids of Selachops flavocinctus Wahlberg, 1844 (Diptera: Agromyzidae) in the Central Urals, Russia. 2 records from Zobellia amurskyensis sp. nov., Zobellia laminariae sp. nov. and Zobellia russellii sp. nov., novel marine bacteria of the family Flavobacteriaceae. 3 records from Collection Crustacea - ZSRO. 6 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 109 records from Distribución actual, estatus poblacional y evaluación del estatus de protección del pavo ocelado (Agriocharis ocellata). 2217 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 119 records from Various insect orders, NEF. 1 records from Celaeno spinosa. 2 records from Event-based biogeography of Eusarcus dandara sp. nov. (Opiliones: Gonyleptidae), an endemic species of the Northern Atlantic Rainforest of Brazil, and its closely related species. 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 1 records from On the Chilopoda from Turkey. 1 records from On some Haploops species collected in the North Atlantic Ocean with the description of Haploops islandica n. sp. (Crustacea: Gammaridea: Ampeliscidae) [Contribution to the knowledge of the Haploops genus. 8.]. 5 records from Rediscovery and redescription of a deep-sea shrimp Lebbeus longidactylus (Kobjakova, 1936) (Crustacea: Decapoda: Caridea: Thoridae) based on material from the Nemuro Strait, southwestern Sea of Okhotsk. 21245 records from SA Fauna (BDBSA). 13 records from A new species of Eigenmannia Jordan and Evermann (Gymnotiformes: Sternopygidae) from the upper rio Paraguai basin. 15953 records from Algae (S). 23 records from Descriptions of larvae of four species of Hydropsyche (Hydropsychidae: Trichoptera) from Thailand. 26017 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 3 records from First record of order Embioptera (Insecta) for the State of Tocantins, Brazil, with description of a new species of Clothoda Enderlein. 10255 records from Araneae Collection. 10 records from First report of some known Trichodinella epizootica Šramek-Hušek, 1953, and Tripartiella Lom, 1959 from the cultured Oranda Gold Fish (Carassius auratus auratus) in India. 1201 records from Registros faunísticos de invertebrados marinos en el SE del Golfo de California. 2560 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 80 records from Museu Paraense Emílio Goeldi - Platyhelminthes Collection. 259 records from Biología poblacional de Isostichopus fuscus (Ludwig, 1875) (Echinodermata: Holothuroidea) en el sur del Golfo de California. 3 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 16568 records from Fungus herbarium, UiB. 116007 records from BMSM Bailey-Matthews National Shell Museum. 2957 records from HSU Wildlife Mammals. 146809 records from OHN. 6000 records from Algas marinas bentónicas de la Península de Yucatán y uso potencial de especies selectas. 30 records from Specimens from India at the University Museum at the University of Bergen. 192273 records from Field Museum of Natural History (Zoology) Mammal Collection. 2 records from Myrmica afghanica (Hymenoptera: Formicidae), a new ant species from Afghanistan.. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 16 records from Bolivian Mimosa (Leguminosae, Mimosoideae): three new species and a species checklist. 1129 records from Upper Silesian Museum, Insect Collection. 378 records from Ichthyologie ZMK. 11472 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1 records from Cesiribacter roseus sp. nov., a pink-pigmented bacterium isolated from desert sand. 657 records from MVZ Hildebrand Collection (Arctos). 19 records from The Dixa inextricata Dyar & Shannon (Diptera: Dixidae) species group, with two new cryptic species from the eastern Nearctic Region. 1 records from Oribates angulatus. 51 records from Packer Collection / Xenochilicola bees, Chile. 1626 records from Ornithologie ZMK. 171692 records from Lund Museum of Zoology (MZLU). 439 records from Museu Paraense Emilio Goeldi - Scorpiones Collection. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from Protozoa ZMK. 281 records from Myriapoda of Costa Rica (INBio). 568 records from Expedición Providencia I - INVEMAR. 2 records from Amphibia ZMK. 623262 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from Nothrus bispinosus. 7 records from Vermes ZMK. 1 records from Oribates badius. 5 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 38 records from Revision of the Taiwanese species of the genus Leptophion Cameron, 1901 (Hymenoptera: Ichneumonidae: Ophioninae), with a discussion of their phenology and distribution. 1 records from Ctenophora ZMK. 1 records from Nothrus bicarinatus. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 382 records from Reptilia ZMK. 39 records from Arachnologie ZMK. 2 records from A new species of the genus Paracypria (Crustacea: Ostracoda: Cypridoidea) from the Fiji Islands. 2 records from Bryozoa ZMK. 8 records from Macropsini (Hemiptera: Cicadellidae) of Thailand, with description of two new species and three new country records. 20991 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 6562 records from FCAB - Herbário Friburguense. 1265 records from Crustacea ZMK. 104 records from Mammalogie ZMK. 2 records from REDESCRIPTION OF TETRAMORIUM ATLANTE CAGNIANT, 1970, NEW STATUS (HYMENOPTERA: FORMICIDAE: MYRMICINAE). 4 records from Tunicata ZMK. 2 records from Two new species within the genus Seira Lubbock, 1869 from Morocco (Collembola, Entomobryidae). 32109 records from Herbier de Nouvelle-Calédonie. 3 records from Pantopoda SMF. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 68 records from Malakologie ZMK. 1158 records from Base de datos y colección de anfípodos (Hyperiidea:Crustacea) de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 61 records from ZUEC-PLA - Coleção de Platyhelmintes do Museu de Zoologia da UNICAMP. 733 records from Catalogue of the family Ologamasidae Ryke (Acari: Mesostigmata). 3 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 10 records from Cnidaria ZMK. 10 records from New Zopheridae (Coleoptera: Tenebrionoidea) from Baltic amber. 165299 records from CAS Invertebrate Zoology (IZ). 16 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 6796 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 4 records from A new canopy-dwelling species of Dendrelaphis (Serpentes: Colubridae) from Sinharaja, World Heritage Site, Sri Lanka. 2 records from Porifera ZMK. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 17 records from Abyssal fauna of the UK-1 polymetallic nodule exploration area, Clarion-Clipperton Zone, central Pacific Ocean: Cnidaria. 13 records from Description of a new species of the genus Chaetostoma from the Orinoco River drainage with comments on Chaetostoma milesi Fowler, 1941 (Siluriformes: Loricariidae). 16621 records from Crustacea collection of National Museum of Nature and Science. 12 records from Echinodermata ZMK. 9 records from Diagnosis of Calagasma Bergroth and Epipedus Spinola with description of Calagasma eclipsa sp. nov. and Epipedus rolstoni sp. nov. (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 895 records from Códigos de barras de hongos ectomicorrízicos de localidades selectas del neotrópico mexicano. 1 records from On centipedes (Chilopoda) of Albania, 2. 28 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 513 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 7 records from A new species of Anacroneuria Klapálek 1909 (Plecoptera: Perlidae) from Espírito Santo State, southeastern Brazil and comments on additional species. 2 records from Endogean and cavernicolous beetles of the Balkans. XVI. A new, anophthalmous species of Neuraphes Thomson, 1859 (Coleoptera: Staphylinidae: Scydmaeninae) from Albania. 1029 records from Freshwater plants of Cameroon. 1 records from On the Chilopoda from Turkey. 4 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 7697 records from MBML-Aves - Coleção de Aves MBML. 287 records from The Sea Ice Fauna of Frobisher Bay, Arctic Canada 1981 and 1982. 41 records from The genus Leucophenga (Diptera, Drosophilidae), part VI: the argentata species group from the East Asia, with morphological and molecular evidence. 12 records from Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution. 940 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 4 records from Uncovering the diversity of the neotropical genus Elaphopsocus (‘ Psocoptera’: Psocidae: Amphigerontiinae): from one to ten species. 89 records from Collection Crustacea - PUM. 19 records from The first case of aggressive mimicry among lamprologines in a new species of Lepidiolamprologus (Perciformes: Cichlidae) from Lake Tanganyika.. 42599 records from Tallinn Botanic Garden. 14420 records from Colección Nacional de Foraminíferos - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 7113 records from Primera fase de actualización de la Colección de Siphonaptera Alfredo Barrera del Museo de Zoología Alfonso Herrera. 1 records from Nothrus convexus. 5 records from Redescription of two European species of Acerentomidae (Protura) belonging to the Italian fauna. 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 200 records from Zoological collection of the National Museum. 1942 records from Western Australia Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 103 records from A revision of the genus Andesipolis (Hymenoptera: Braconidae: Mesostoinae) and redefinition of the subfamily Mesostoinae. 2031 records from Creación de la base de datos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, y de la reserva de la biosfera Islas del Golfo de California para el grupo de los mamíferos. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 2 records from A review of the ant genus Harpegnathos Jerdon, 1851 (Hymenoptera: Formicidae) in the Philippines, with the description of two new species. 2090 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 2223 records from Colección de Zoología Invertebrados - Otros invertebrados. 9 records from Chenopodium vulvaria. 2231 records from UCM Bird Eggs/Nests Collection (Arctos). 11251 records from Herbarium areqvipense (HUSA). 21134 records from NCSM Birds Collection. 1000 records from Colección Limnológica del Chocó. 75 records from Conocimiento de la diversidad y distribución actual del maíz nativo en Nuevo León. 163 records from A review of Lamyra Loew (Diptera: Asilidae: Laphriinae). 1328 records from Colección de Invertebrados Cenpat (CNP-INV). 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 2 records from A new hydryphantid genus from the Tien Shan Mountains of Kazakhstan (Acari, Hydrachnidia: Hydryphantidae). 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 77122 records from Lepidoptera (Rhopalocera y Heterocera) de áreas prioritarias para la conservación en la Península de Yucatán, con registros de adultos y estados inmaduros. 5338 records from CHAS Mammalogy Collection (Arctos). 118 records from Taxonomy and immature stages of the Platystomatidae (Diptera: Tephritoidea) of Israel. 31590 records from UAM Bird Collection (Arctos). 688 records from Algae, Norwegian College of Fishery Science. 150 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 9 records from Corumbataia britskii (Siluriformes: Loricariidae: Hypoptopomatinae) a new species from the upper Rio Parana basin, Mato Grosso do Sul, Central Brazil.. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 1 records from A new myrmicine ant genus from Malaysia with uncertain affinities (Hymenoptera: Formicidae).. 3438 records from Norwegian Biodiversity Information Centre - Other datasets. 95 records from Eight new species of Andrena Fabricius (Hymenoptera: Apoidea: Andrenidae) from Israel—a Mediterranean hotspot for wild bees. 30926 records from Annelida collection of National Museum of Nature and Science. 377 records from Herbario MAIA, colección de Eucaliptus del INIA-CIFOR. 90 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 6 records from Coendutermes tucum Fontes (Isoptera, Termitidae, Nasutitermitinae): description of the imago caste and additional notes. 28796 records from MPM Herpetology. 2 records from First Jurassic grasshopper (Insecta, Caelifera) from China. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 1 records from Die Chilopodenfauna Griechenlands. 2 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 4 records from The species of the genus Diamesa (Diptera, Chironomidae) known to occur in Italian Alps and Apennines. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 6421 records from ZUEC-BIV - Coleção de Bivalvia do Museu de Zoologia da UNICAMP. 23 records from Description of Cathorops manglarensis, a new species from the Colombian Pacific, with redescription of Cathorops multiradiatus (Siluriformes; Ariidae).. 2097 records from Base de datos de la familia Cactaceae de la Península de Baja California, México. 4 records from Taxonomy of two endemic Indian skinks, Eutropis bibronii (Gray, 1838) and E. nagarjunensis (Sharma, 1969) (Reptilia: Scincidae), including redescriptions of their types. 251 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 2 records from Two New Variegated Snailfishes of the Genus Careproctus (Teleostei: Scorpaeniformes: Liparidae) from the Aleutian Islands, Alaska. 111 records from New distributional data on aquatic and semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha & Nepomorpha) from South America. 8 records from Torpedo formosa sp. nov., a new species of electric ray (Chondrichthyes: Torpediniformes: Torpedinidae) from Taiwan.. 7000 records from CCBER Ornithology Collection. 1322 records from Sistematización de la Colección de Algas Marinas del Centro Interdisciplinario de Ciencias Marinas CICIMAR-IPN. 1677 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 6 records from Description of two new species of Coeliccia from Vietnam (Odonata: Platycnemididae). 2954 records from Geneva Herbarium – Burnat Herbarium (G-BU). 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 2502 records from ISM Herpetology Collection. 63874 records from La familia Asteraceae en México. Fase VI. 21694 records from arim. 1282 records from Computarización de Pterópodos (Thecosomata: Gastropoda) del Caribe de México y Belice. 4 records from A new species of the genus Bothrioplana (Platyhelminthes: Bothrioplanida: Bothrioplanidae) and a new species of the genus Pentacoelum (Tricladida: Bdellouridae) from southern China. 6812 records from Invertebrate collection of University of Oulu Zoological Museum. 8887 records from The tunicates collection (IT) of the Muséum national d'Histoire naturelle (MNHN - Paris). 35030 records from Naturalis Biodiversity Center (NL) - Mammalia. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 207 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 2 records from A redescription of Lophostica mauriciana Simon, 1902 (Araneae: Salticidae). 1666051 records from Museum of Comparative Zoology, Harvard University. 623 records from BRFC Black Rock Forest Consortium Herbarium. 12542 records from Herbarium of the Université Libre de Bruxelles. 7538 records from Actualización de la colección poliquetológica de la Universidad Autónoma de Nuevo León. 8102 records from tef-database. 48 records from Tardigrada collection of National Museum of Nature and Science. 684 records from Estudio de la diversidad genética y su distribución de los maíces criollos y sus parientes silvestres en Michoacán. 140 records from Three new percid fishes (Percidae: Percina) from the Mobile Basin drainage of Alabama, Georgia, and Tennessee.. 58044 records from Naturalis Biodiversity Center (NL) - Cnidaria. 13 records from First report of two deep-sea shrimps of the genus Acanthephyra A. Milne-Edwards, 1881 (Crustacea: Decapoda: Acanthephyridae) from southwestern Atlantic. 60 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 718 records from HSU Vertebrate Museum Amphibian Collection. 1 records from Amycolatopsis marina sp. nov., an actinomycete isolated from an ocean sediment. 5241011 records from Australia's Virtual Herbarium. 16 records from Moenkhausia pankilopteryx, new species from rio Tocantins drainage, Brazil (Ostariophysi: Characiformes, Characidae).. 13503 records from Collection of various insect orders, Natural History Museum, University of Oslo. 36669 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 292 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 9948 records from Bees of Canada / Gschwendtner property collection. 2 records from Description of a new genus and two new species of alpheid shrimps from Guam (Crustacea, Decapoda) *. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 363 records from The cicadas (Hemiptera: Cicadidae) of India, Bangladesh, Bhutan, Myanmar, Nepal and Sri Lanka: an annotated provisional catalogue, regional checklist and bibliography. 3 records from Two new Cambodian semi-aquatic earthworms in the genus Glyphidrilus Horst, 1889 (Oligochaeta, Almidae), based on morphological and molecular data. 38841 records from Herbier de Strasbourg. 1 records from Flora of Suriname, volume VI, part I. 39 records from New taxonomic and faunistic data on the Himalayan Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae). 10 records from The crane fly genus Libnotes Westwood, 1876 (Diptera: Limoniidae) for Korea including two new species and an identification key. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 8 records from The cladorhizid fauna (Porifera, Poecilosclerida) of the Caribbean and adjacent waters. 197991 records from Vascular Plant Herbarium, UiB. 86 records from Base de datos de Rana catesbeiana.. 90 records from Revision of the genus Centistes (Hymenoptera: Braconidae: Euphorinae: Centistini) of Costa Rica. 1808 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 7 records from Applying n-dimensional hypervolumes for species delimitation: unexpected molecular, morphological, and ecological diversity in the Leaf-Toed Gecko Phyllodactylus reissii Peters, 1862 (Squamata: Phyllodactylidae) from northern Peru. 55 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 5924 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 7728 records from Scarabaeoidea y colección de tipos de la colección entomológica del Centro de Estudios en Zoología, Universidad de Guadalajara. 56302 records from Kathryn Kalmbach Herbarium. 1 records from Nothrus palliatus. 6 records from Cobitis nalbanti, a new species of spined loach from South Korea, and redescription of Cobitis lutheri (Teleostei: Cobitidae). 6211 records from NMMNH Mammal. 199111 records from Ichthyology Collection - Royal Ontario Museum. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 2087 records from Banco de Germoplasma del Jardín Botánico Atlántico. 15 records from Chenopodium. 732 records from Ictiofauna Lermense. 4900 records from Actualización de la colección ictiológica de Ecosur-Chetumal. 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 16 records from A description of two new species of the genus Erenna (Siphonophora: Physonectae: Erennidae), with notes on recently collected specimens of other Erenna species. 338 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 200913 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 10 records from Fishes in MZNA-VERT: foraging ecology of the kingfisher. PhD project, Antonio Vilches. 260950 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 6004 records from Colección Limnológica Universidad de Antioquia. 98686 records from CAS Ornithology (ORN). 20957 records from CHAS Herpetology. 463 records from Nemátodos acuáticos de vida libre de la cuenca de la Laguna de Términos, Campeche. 7 records from Three new species of tribe Odynerini (Hymenoptera, Vespidae, Eumeninae) from the Neotropical Region. 1 records from Zetes morticinus. 216 records from Ecología e historia natural de Schistocerca americana socorro y S. piceifrons piceifrons en Isla Socorro. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 7 records from Pseudochromis lugubris and P. tonozukai, two new dottyback fish species from the Indo-Australian Archipelago (Perciformes: Pseudochromidae: Pseudochrominae).. 22166 records from Natural History Museum Maastricht (NL) - Herbarium. 29171 records from Naturalis Biodiversity Center (NL) - Collembola. 13 records from The first data on species diversity of leeches (Hirudinea) in the Irtysh River Basin, East Kazakhstan. 1910784 records from Consortium of California Herbaria. 3 records from New synonymies in the plant bug family Miridae (Hemiptera: Heteroptera) from Northern China. 2 records from The first Turcolana Argano & Pesce, 1980 (Isopoda: Cirolanidae) from the Greek mainland. 11 records from Description of a new species of Priolepis (Perciformes: Gobiidae) from the Red Sea, a new record of Priolepis compita, and a distributional range extension of Trimma fishelsoni. 258 records from Cnidarios del proyecto Macrofauna Corpoguajira. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 3 records from A remarkable new species of the genus Lepisiota Santschi (Hymenoptera: Formicidae) from Oman and the United Arab Emirates with a key to the Arabian species. 1 records from Zetes latipes. 27 records from A new species of crayfish in the genus Orconectes (Decapoda: Cambaridae) from the Tennessee River Drainage with comments on and key to members of the O. juvenilis Species Complex. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 6 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 59815 records from Tasmanian Museum and Art Gallery provider for OZCAM. 30 records from New species of Hercostomus Loew, 1857 (Dolichopodidae, Diptera) from Japan. 3317 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 6 records from Mammalia (JNHM-MM). 70101 records from Kyushu University Museum Coleoptera Collection. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 25 records from Revision of the Malagasy species of Homalium sect. Eumyriantheia Warb. (Salicaceae). 3002 records from Colección de Peces Universidad Católica de Oriente. 69622 records from Fundación Miguel Lillo - Colección Entomológica. 311 records from Genotipificación de especies de la ictiofauna del Sistema Pánuco-Tamesí a través de la generación del código de barras de ADN mitocondrial. 3 records from Redescription of Lystrocteisa Simon, 1884 (Araneae: Salticidae) from New Caledonia. 409 records from Herbario MAIA, colección de Quercus del INIA-CIFOR. 25543 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 15257 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán. 2 records from Discovery of a new millipede species in northern Vietnam, and the proposal of a new genus, Parariukiaria (Diplopoda, Polydesmida, Xystodesmidae). 5310 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 2 records from Neue Milbenarten aus Kärnten. 9787 records from Finnish Entomological Database: Hymenoptera. 163 records from Barcode de Bambúes nativos de México. 73 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 2 records from Re-description of the Arctic tardigrade Tenuibiotus voronkovi (Tumanov, 2007) (Eutardigrada; Macrobiotidea), with the first molecular data for the genus. 10 records from Revision of the spider crab genus Sargassocarcinus Ward, 1936 (Crustacea: Brachyura: Epialtidae). 48 records from Descriptions of three larvae of Osmylus species from Japan (Neuroptera: Osmylidae), with a proposed naming system for the larval sclerites. 1860 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 1 records from Hypochthonius rufulus. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 1 records from Oribates ovatus. 28 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 8 records from A new Mapinguari Papavero & Wilcox (Diptera, Mydidae, Mydinae) from Minas Gerais State, Brazil. 1 records from Hoplophora crinita. 172102 records from CONN. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 35840 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from A new shallow water species of Artemisina Vosmaer, 1885 (Microcionidae, Demospongiae; Porifera) from Northeastern Brazil. 17252 records from BioGIS - Vascular plants - HUJ Herbarium. 1077 records from BioGIS - Fish - HUJ collections. 3753 records from Registros biológicos de especies de plantas del Bosque Seco en Colombia presentes en el Herbario JBGP. 4 records from Leptophlebiidae (Ephemeroptera) from Roraima State, Brazil: description of two new species of Ulmeritoides Domínguez, 1991. 1972 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 418 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 50880 records from H.A. Stephens Herbarium. 4 records from A new ant genus from the southwestern United States.. 314 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 16 records from Mollusca Colelction of the Seto Marine Biological Laboratory, Kyoto University. 13968 records from NYSM Birds. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 2 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 1896 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 22 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 21 records from Morphological and molecular data reveal the cryptic diversity among populations of Aegla paulensis (Decapoda, Anomura, Aeglidae), with descriptions of four new species and comments on dispersal routes and conservation status. 124768 records from Recent Invertebrates Specimens. 9744 records from Actualización de la base de datos de la Colección de mamíferos del Museo de Zoología 'Alfonso L. Herrera'. 1369 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 319 records from HTSAw - Xiloteca do Trópico Semiárido. 3 records from Description of a new species of Dascillus Latreille from Sichuan, China (Coleoptera: Dascillidae). 1733 records from Birds collection of Abiko City Museum of Birds. 23046 records from Hemipteran specimens of Iwate Prefectural Museum. 2043 records from Mollusca Collection of Natural History Museum and Institute, Chiba. 105 records from On the Nazeris fauna of Zhejiang, China (Coleoptera, Staphylinidae, Paederinae). 30000 records from Birds collection of Yamashina Institute for Ornithology. 4 records from Primi reperti del genere Calyptomyrmex Emery nel subcontinente Indiano. 1000 records from Mollusca Specimens of Oiso Municipal Museum. 22 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 2115 records from Algae specimenｓ database of Shizuoka Prefecture Museum of Natural History. 35 records from Catalogue of the Teratomyzidae (Diptera, Opomyzoidea) of the World. 96 records from Taxonomic revision and phylogeny of the ant genus Prenolepis (Hymenoptera: Formicidae). 2 records from A new terrestrial planarian species of the genus Marionfyfea (Platyhelminthes: Tricladida) found in Europe. 7 records from Partial redescription of pontoniine shrimps Cuapetes nilandensis (Borradaile, 1915) and Cuapetes seychellensis (Borradaile, 1915) (Decapoda: Palaemonidae: Pontoniinae) with remarks on taxonomic status of Cuapetes Clark, 1919 and Kemponia Bruce, 2004. 12 records from Asian pheretimoid earthworms in North America north of Mexico: An illustrated key to the genera Amynthas, Metaphire, Pithemera, and Polypheretima (Clitellata: Megascolecidae). 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 701 records from El género Festuca (Poaceae: Pooideae) en México. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 17 records from A new species of the Cyrtodactylus (Geckoella) collegalensis (Beddome, 1870) complex (Squamata: Gekkonidae) from Western India. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 2276 records from UFRN-Fungos - Herbário UFRN - Fungos. 480 records from Spiders of French Guiana. 123 records from Taxonomy of the Mexican species of Thyreocephalus Guérin-Méneville (Coleoptera: Staphylinidae, Xantholinini). 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 11 records from A new rainbowfish (Teleostei: Melanotaenioidei: Bedotiidae) from the southeastern highlands of Madagascar, with comments on the biogeography of Bedotia.. 18247 records from Base de datos del Herbario CIQR de El Colegio de la Frontera Sur, unidad Chetumal. 43 records from A Unique Nest-Protection Strategy in a New Species of Spider Wasp. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 69 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 10 records from Maculabatis ambigua sp. nov., a new whipray (Myliobatiformes: Dasyatidae) from the Western Indian Ocean. 3 records from Salticidae from the Himalayas. The genus Hasarius Simon, 1871 (Araneae: Salticidae). 6028 records from Coleção de Polychaeta do Museu Nacional. 2 records from Description of a new species of Thevenetimyia (Diptera: Bombyliidae) from Madagascar, with a revised checklist of Madagascan bee fly fauna. 164 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 29 records from A Revision of the Genus Synagelides Strand, 1906 (Araneae, Salticidae) in Korea. 1 records from A case of disjunct montane linyphiid species (Araneae) in the Palaeotropics, with notes on synonymy and the description of a new species. 11 records from Anticyphon gen. nov., a new genus of Scirtidae (Coleoptera: Scirtoidea) inhabiting high altitude Andean cloud forests and páramo formation. 7629 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 2059 records from Flora of Japan Specimen Database. 41 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 61 records from The water mite family Aturidae Thor (Acari: Hydrachnidia) from Ghana, with the description of twelve new species. 6774 records from Colección Nacional de Paleopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 7 records from A remarkable new lichenophilous Pamexis species from the Hantam Karoo of South Africa (Neuroptera: Myrmeleontidae: Palparini). 211 records from Estructura genética y conservación de la tortuga negra Chelonia agassizi en el Pacífico mexicano. 1594 records from Musée Vert ornithology collection. 21749 records from University of Lethbridge Herbarium (LEA). 1 records from Murcia trimaculata. 15 records from Two new species and new records of the genus Paraopisthosyllis Hartmann-Schröder, 1991 (Annelida: Syllidae) from northeastern Brazil and Philippine Islands. 1318 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 258 records from Determinación de la distribución potencial de las especies nativas e introducidas de bambú en México.. 10343 records from KUBI Ichthyology Tissue Collection. 1900 records from Fungi Collection. 111981 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 84255 records from AM: Terrestrial Insect Collections (1896-2000). 780 records from Comportamiento espacio-temporal de la densidad fitoplanctónica en el año 2015 Magdalena, Colombia. 4 records from Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932. 230748 records from Estonian Museum of Natural History. 603 records from Registros preliminares del "Catálogo de cangrejos ermitaños del mar Caribe colombiano". 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 280 records from Naturalis Biodiversity Center (NL) - Orthopteroidea. 5681 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 4745 records from Collection botanique Le Grand A. (BOUM). 23 records from Deep-sea squat lobsters of the genus Paramunida Baba, 1988 (Crustacea: Decapoda: Munididae) from north-western Australia: new records and description of three new species. 36 records from A revision of the Eudarcia glaseri - species group (Lepidoptera, Meessiidae) with description of two new species from Greece and Crimea. 1752 records from Herbier National de Mauritanie (HNM). 1266 records from Bolivian Amazon lowland fish metacommunity data. 276 records from Código de barras de ocho complejos de especies de aves mexicanas. 4 records from A new species of the ant genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae) from the Caribbean region. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 61 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 850 records from Shellfish (NHMK-MS). 25181 records from University of California Museum of Paleontology. 3 records from A new species of the spider genus Plator (Trochanteriidae) from south China. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 26 records from A new species of Oreodera Audinet-Serville, 1835 from Ecuador (Coleoptera, Cerambycidae, Lamiinae) and new geographical records. 81659 records from UCT: Southern African Butterfly Conservation Assessment (1815-2009). 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 7 records from Bodotria jejuensis sp. nov. (Crustacea, Cumacea, Bodotriidae), a new Korean cumacean. 7 records from Kryptolebias sepia n. sp. (Actinopterygii: Cyprinodontiformes: Rivulidae), a new killifish from the Tapanahony River drainage in southeast Surinam.. 1227 records from M. Andrew Johnston Collection. 37325 records from Phytoplankton from the White Sea, Barents Sea, Norwegian Sea and Arctic Basin 1993-2003. 1052 records from Biodiversidad de coleópteros y arañas de las Sierras de Taxco-Huautla. 371 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 374 records from Macroarthropods, Godthåbsfjorden (Nuup Kangerlua) 2013, Greenland. 1 records from Asya hayvanlari ve zoogeografiyasi hakkinda. Asiatische Beiträge. VIII.. 1901 records from Flora acuática vascular del estado de Morelos, México. 7046 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 1 records from Zur Kenntnis der Lithobiiden. 12 records from Hybothoracaphis, a new genus of Nipponaphidini (Hemiptera, Aphididae, Hormaphidinae) from China and its phylogenetic placement based on multiple genes. 20 records from Molecular and morphological identification of pistachio armored scale insects (Hemiptera: Diaspididae), with description of a new species. 2 records from Two new species of genus Joruma McAtee (Hemiptera: Cicadellidae: Typhlocybinae) from Viçosa, Minas Gerais State, Brazil. 962 records from Inventarios florísticos en Baja California Sur (II): Vegetación costera. 33 records from The identity of Pseudomystus moeschii (Boulenger, 1890), with the description of two new species of bagrid catfishes from Southeast Asia (Teleostei: Bagridae).. 6001 records from Computarización de la colección de hongos de ECOSUR, en el estado de Chiapas. 43857 records from Mammals housed at MHNG, Geneva. 21132 records from DMNS Marine Invertebrate Collection (Arctos). 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 2860 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves (MFA-ZV-Or). 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 1151 records from Odonata of the Congo River 2010 expedition. 1244 records from Mosquitoes_of_French_Guiana. 6337 records from Actualización de la base de datos y la colección de hipéridos (Crustacea) y sifonóforos (Cnidaria) del Atlántico mexicano. 5812 records from Las monocotiledóneas mexicanas, una sinopsis florística. 1 records from Cladorhiza corallophila sp. nov., a new carnivorous sponge (Cladorhizidae, Demospongiae) living in close association with Lophelia pertusa and Madrepora oculata (Scleractinia). 981 records from Herbier du muséum Henri-Lecoq de Clermont-Ferrand . 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 34695 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr).. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 3 records from New findings of Hexalona-branch representatives in Brazil, with a description of Prenda gen. nov. (Crustacea: Anomopoda: Aloninae). 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 99225 records from ALCB - Herbário Alexandre Leal Costa. 800 records from Reevaluación taxonómica de las especies de algas coralinas (Corallinales; Rhodophyta) que forman mantos de rodolitos en el Golfo de California, México. 56 records from Onychophora of Costa Rica (INBio). 3 records from New records and species of Crepidodera Chevrolat (Coleoptera: Chrysomelidae) in Eocene European amber, with a brief review of described fossil beetles from Bitterfeld amber. 141 records from Bathyal Mollusca from the cold-water coral biotope of Santa Maria di Leuca (Apulian margin, southern Italy). 245 records from Coleção de Platyhelminthes do Museu Nacional - UFRJ. 6325 records from HUSC - Herbário Unisanta. 25128 records from rmca-albertine-rift-butterflies. 32 records from A new cave species of Coecobrya Yosii (Collembola, Entomobryidae, Entomobryinae) from South Africa, with an identification key to the genus. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 197133 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 150 records from Museu Paraense Emilio Goeldi - Crocodilia Collection. 4 records from A new genus and species of Acaenitini (Hymenoptera, Ichneumonidae, Acaenitinae) from China. 23 records from Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution. 8815 records from HPBR - Herbário Padre Balduino Rambo. 131642 records from mel. 1509 records from Pamphagidae (Orthoptera: Acridoidea) from the Palaearctic Region: taxonomy, classification, keys to genera and a review of the tribe Nocarodeini I. Bolívar. 11 records from A new biogeographically disjunct giant gecko (Gehyra: Gekkonidae: Reptilia) from the East Melanesian Islands. 1 records from Nothrus piceus. 104 records from Catalogue of the type specimens of Bufonidae and Megophryidae (Amphibia: Anura) from research collections of the Zoological Institute, Russian Academy of Sciences. 1307 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 11 records from Thorectinae (Porifera: Demospongiae: Dictyoceratida) from Northeastern Brazil: two new species and transfer of Scalarispongia cincta (Boury-Esnault, 1973) to the genus Thorecta Lendenfeld, 1888. 1442 records from Aves de México I. 380347 records from Estonian University of Life Sciences. 229511 records from Essig Museum of Entomology. 207317 records from CAS Ichthyology (ICH). 1401 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 10468 records from The Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 923 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 5606 records from Caracterización biológica del Monumento Natural Yaxchilán como un elemento fundamental para el diseño de su plan rector de manejo. 9 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 113 records from Distribution data of Arctic species of genus Microporella and Pseudoflustra gathered from museum collections. 506 records from Base de datos sobre los hongos anamorfos de restos de vegetales del bosque mesófilo del estado de Veracruz. 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 8 records from Records of Wenchengia (Lamiaceae) from Vietnam. 3 records from A new permopsocidan genus and species from the Late Permian of Australia (Insecta: Acercaria: Psocidiidae). 1 records from On the Chilopoda from Turkey. 69 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 8120 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 10234 records from Collection entomologique Barthélémy. 360 records from Order Araneae. 1 records from A new Otocinclus (Siluriformes: Loricariidae: Hypoptopomatinae) from the Rio Juruena Basin, central Brazil. 11 records from Himantura hortlei n. sp., a new species of whipray (Myliobatiformes: Dasyatidae) from Irian Jaya, Indonesia.. 2414 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 169 records from An annotated checklist of the Collembolan fauna of Thailand. 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 10 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 2 records from The polyps of Oceania armata identified by DNA barcoding (Cnidaria, Hydrozoa). 1166 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 278 records from Fishes in MZNA-VERT: baseline freshwater sampling campaigns. 1915 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 14 records from Taxonomic revision of the Dasypus kappleri complex, with revalidations of Dasypus pastasae (Thomas, 1901) and Dasypus beniensis Lönnberg, 1942 (Cingulata, Dasypodidae). 15972 records from DMNS Mammal Collection (Arctos). 1 records from Indothrix Krombein, 19 57 (Hymenoptera, Chrysididae) newly recorded genus from China, with description of one new species. 19 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 7 records from Benthic myodocopid Ostracoda (Philomedidae) from the Southern Ocean. 7061 records from Inventario ictiofaunístico en tres regiones hidrológicas prioritarias de la Cuenca del Grijalva-Usumacinta en el estado de Chiapas. 20 records from Cyatta abscondita: Taxonomy, Evolution, and Natural History of a New Fungus-Farming Ant Genus from Brazil. 129 records from Mammalia (KNAM-MM). 1 records from Nothrus mutilus. 10 records from Supplement to the knowledge of the genus Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) of China. 4 records from Revised taxonomic status of Eidophasia zukowskyi Amsel, 1938 (Lepidoptera, Plutellidae) with first description of its male and female genitalia. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 118 records from An annotated checklist of Malachiidae (Coleoptera: Cleroidea) from Iran. 2052 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 60109 records from TNHC Ichthyology Collection. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 22 records from Review of amphipods of the Melita group (Amphipoda: Melitidae) from the coastal waters of Sakhalin Island (Far East of Russia). III. Genera Abludomelita Karaman, 1981 and Melita Leach, 1814. 267 records from PSUZC-Reptile Collection. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 7 records from Cerapanorpa, a new genus of Panorpidae (Insecta: Mecoptera) with descriptions of three new species. 1 records from On the gonotheca of Egmundella producta (G. O. Sars, 1874) n. comb. (Cnidaria, Hydrozoa). 163 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 23 records from Description of larvae of genera Stenelmis, Ordobrevia and Nomuraelmis (Coleoptera: Elmidae: Elminae) of Japan with their molecular taxonomy. 3 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 2826 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 8 records from Lathrolestes Förster, 1869 (Hymenoptera, Ichneumonidae) from Brazil, with description of two new species and a key to the Neotropical species. 50805 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 1 records from Oribates orbicularis. 5036 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 3 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 36138 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 64542 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 75 records from The true identity of Dixa modesta Johannsen (Diptera: Dixidae) resolved: synonymy of Dixa similis Johannsen, designation of the Dixa ubiquita species group, and description of three new eastern Nearctic species. 1 records from Papilio Sticheli nov. spec. aut subsp.. 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 753 records from Estudio taxonómico de las aves y mamíferos del Valle Cuatrociénegas, Coahuila, México. 4 records from Arthropoden aus südostalpinen Höhlen.. 51 records from Revision of the Nearctic endemic Formica pallidefulva group.. 881 records from Moluscos Marinhos de Augusto Nobre. 2 records from Kochertgraben II. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 16 records from A review of the systematics of western North Pacific angel sharks, genus Squatina, with redescriptions of Squatina formosa, S. japonica, and S. nebulosa (Chondrichthyes: Squatiniformes, Squatinidae).. 355 records from Carábidos (Coleoptera: Carabidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 817 records from Actualización del inventario de peces dulceacuícolas del río Papaloapan. 2 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 14 records from A new and endangered species of Kingsleya Ortmann, 1897 (Crustacea: Decapoda: Brachyura: Pseudothelphusidae) from Ceará, northeastern Brazil. 12 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 25 records from Morphologische Daten von Natrix. 47706 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 1680 records from Benthic Microalgae Chukchi Sea, 1972. 300 records from Estudio monográfico de los gasteromicetos del noroeste de Baja California, México. Provincia Californiana. 47 records from Revised diagnosis of the genus Bangana Hamilton, 1822 (Pisces: Cyprinidae), with taxonomic and nomenclatural notes on the Chinese species.. 39 records from A review of Sri Lankan Brignolia including the description of four new species (Araneae: Oonopidae). 6198 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 14 records from Three new species of the seasonal killifish genus Simpsonichthys, subgenus Hypsolebias (Teleostei: Cyprinodontiformes: Rivulidae) from the rio Paracatu drainage, rio São Francisco basin, Brazil.. 1 records from Hoplophora ardua. 8438 records from HSU Vertebrate Museum Mammals Collection. 709 records from Upper Silesian Museum, Bird Collection. 2 records from Tanypus urszulae, a new Tanypodinae (Diptera: Chironomidae) from the Neotropical Region. 1 records from A new jellynose, Ateleopus edentatus, from the western Pacific Ocean (Teleostei: Ateleopodiformes: Ateleopodidae). 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 6717 records from LSUMZ Mammal Tissues. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 1120 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 1 records from A new mawsoniid coelacanth (Actinistia) from the Upper Cretaceous of Southern France. 346 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 1140 records from Flora (vascular) y fauna (aves) de los Parques Nacionales del estado de Baja California: Constitución de 1857 y Sierra San Pedro Mártir. 138 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 12 records from Peces batoideos de la plataforma continental del Golfo de Tehuantepec. 6 records from A review of the Macropes Motschulsky (Hemiptera: Lygaeoidea: Blissidae) from China, with descriptions of three new species. 1 records from Murcia ephippiata. 30 records from New talitrids from South Africa (Amphipoda, Senticaudata, Talitroidea, Talitridae) with notes on their ecology. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 20 records from BIRDRACE Birding Bentheim. 58368 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 1 records from Diagnosies provisoires de quelques espèces nouvelles de fourmis de Madagascar, récoltées par M. Grandidier.. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 17 records from Hydrolagus mccoskeri sp. nov., a new species of chimaeroid fish from the Galápagos Islands (Holocephali: Chimaeriformes: Chimaeridae).. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 996 records from Colección científica de diatomeas bentónicas de la Bahía de la Paz, BCS. 2 records from A synoptic revision of the Malagasy endemic genus Socratina Balle (Loranthaceae). Candollea 69: 65 - 73. In English, English and French abstracts.. 5 records from First Canadian record of the water mite Thermacarus nevadensis Marshall, 1928 (Arachnida: Acariformes: Hydrachnidiae: Thermacaridae) from hot springs in British Columbia. 396 records from Colección de Entomología - Auchenorrhyncha. 20 records from BIRDRACE Die TUErteltauben. 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 1 records from Larva of one of the world’s rarest and most threatened damselflies: Spesbona angusta (Odonata: Platycnemididae). 16326 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 184 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s.l., Scelioninae). 6325 records from Colección Entomológica de la Universidad de Antioquia. 5749 records from NX - Herbário Nova Xavantina. 97 records from Evaluación de las categorías de protección de la familia Iridaceae. 2952 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 4109 records from Colección de mamíferos de la Universidad del Valle. 4956 records from NRM-Herpetology. 14237 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc).. 50 records from Review of the genus Signoretia (Hemiptera: Cicadellidae: Signoretiinae) of the Oriental region with description of nine new species. 4344 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 11 records from Balantiocheilos ambusticauda, a new and possibly extinct species of cyprinid fish from Indochina (Cypriniformes: Cyprinidae).. 2 records from Two new species of Dactylonotus Parent, 1934 (Diptera: Dolichopodidae) from South Africa and a key to Afrotropical species. 69 records from Review of the genus Namadytes Hesse, 1969 (Insecta: Diptera: Mydidae: Syllegomydinae). 6 records from Status of the genus Macroramphosus (Syngnathiformes: Centriscidae) in the eastern Mediterranean Sea.. 1294 records from Global Butterfly Information System (GloBIS). 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 425 records from A revision of Malagasy species of Anochetus Mayr and Odontomachus Latreille (Hymenoptera: Formicidae).. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 1770 records from Schmidt Museum of Natural History_Birds. 15 records from An updated checklist of the Recent non-marine Ostracoda (Crustacea) of Iran, with a redescription of Eucypris mareotica (Fischer, 1855). 8613 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 5 records from Motuotrichius yangi, a new genus and species from southeastern Tibet, China (Coleoptera: Scarabaeidae: Cetoniinae: Trichiini). 8 records from Whip spiders (Amblypygi, Arachnida) of the Western Palaearctic—a review. 2486 records from Hawaiian Algal Database. 7331 records from Base de datos de las pteridofitas del estado de Veracruz, México. 7 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 1 records from Arthropoden aus südostalpinen Höhlen.. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 1040 records from Anfibios y Reptiles reportados en humedales del departamento de Córdoba. 1 records from A new species of Danothrips from Southwestern China (Thysanoptera: Thripidae). 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 2877 records from Flea collection of Slovenian Museum of Natural History (Slovenia only). 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 14 records from Four new species of the subfamily Gryllacridinae (Orthoptera: Gryllacrididae) from China. 186345 records from Bryophyte herbarium, NTNU University Museum. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 3 records from A new species of whiptail stingray of the genus Dasyatis Rafinesque, 1810 from the Southwestern Atlantic Ocean (Chondrichthyes: Myliobatiformes: Dasyatidae).. 36 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 26 records from A new trapdoor spider species from the southern Coast Ranges of California (Mygalomorphae, Antrodiaetidae, Aliatypus coylei, sp. nov,), including consideration of mitochondrial phylogeographic structuring. 12 records from Description of a species of Fabaeformiscandona (Ostracoda, Crustacea) from Kushiro Marsh, Hokkaido, Japan, with the nearly complete mitochondrial genomic sequence. 1 records from Celaeno detrita. 4 records from A new species of treefrog (Litoria) from Cape York Peninsula, Australia. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 7380 records from University of Ghent - Zoology Museum - Invertebratacollectie. 348 records from Diplopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 22 records from A new species of Holotachysphex de Beaumont, 1940 (Hymenoptera, Apoidea, Crabronidae) from Iran with identification key to species. 2 records from A world catalogue of Aholcocerus Yakovlev, 2006 (Lepidoptera, Cossidae) with description of a new species from Indonesia. 45003 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe).. 656321 records from Illinois Natural History Survey Insect Collection. 24 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 19 records from Two sympatric species of Antrodiaetus from southwestern North Carolina (Araneae, Mygalomorphae, Antrodiaetidae). 2 records from An extraordinary new genus and species of spider wasps (Insecta: Hymenoptera: Pompilidae) from Southeast Asia. 25596 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv).. 65535 records from OAC-BIO Herbarium. 2 records from Arthropoden aus südotsalpinen Höhlen gesammelt von Karl Strasser. 4. Aufsatz. 70022 records from Bryophyte herbarium, Oslo (O). 16276 records from Coleoptera collection of Uunio Saalas. 124 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 269 records from The species of the Hypostomus cochliodon group (Siluriformes: Loricariidae).. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 25906 records from VIC - Herbário da Universidade Federal de Viçosa. 17 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 1 records from Nothrus scaliger. 2445 records from V. N. Karazin National University. 40 records from ZUEC-NEM - Coleção de Nemertea do Museu de Zoologia da UNICAMP. 6 records from On the Chilopoda from Turkey. 1156 records from Colección Entomológica de la Universidad Tecnológica del Chocó. 182 records from Revision of the ant genus Mayriella.. 2 records from Typhlichthys eigenmanni Charlton, 1933, an available name for a blind cavefish (Teleostei: Amblyopsidae), differentiated on the basis of characters of the central nervous system.. 1536 records from Diversidad de orquídeas en la región El Momón-Margaritas-Montebello, Chiapas, México. 84 records from New species and new records of Cumacea (Crustacea: Peracarida: Cumacea) from mesophotic reefs of Puerto Rico and U. S. Virgin Islands, Caribbean Sea. 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 10 records from A new record of Siler collingwoodi (Araneae: Salticidae) from Japan. 1553 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 1054 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 53173 records from Naturalis Biodiversity Center (NL) - Diptera. 16 records from Review of the ant genus Rogeria (Hymenoptera: Formicidae) in Guyana.. 98 records from Códigos de barras del ADN de especies mexicanas del Phylum Rotifera: (Rotifera: Monogononta). 310 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 2355 records from Colección Ictiológica del CENPAT-CONICET. 7 records from A new species of Cactopinus Schwarz from central Mexico (Coleoptera: Curculionidae: Scolytinae). 4207 records from CASES2003_2004. 1 records from Oribates punctum. 55231 records from Herbario de la Universidad de Granada: GDA. 13 records from New Species and Records of Costa Rican Featherwing Beetles (Coleoptera: Ptiliidae). 10 records from Five new species of genus Encarsia Förster from China (Hymenoptera: Aphelinidae). 4 records from A new species of Ergasilus von Nordmann, 1832 (Copepoda: Cyclopoida) from the gills of a dasyatid ray, Himantura oxyrhyncha (Sauvage, 1878) from West Kalimantan, Indonesia. 4062 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 53 records from On the taxonomy of southern South American species of the wolf spider genus Allocosa (Araneae: Lycosidae: Allocosinae). 8 records from Diversidad de bacterias fotótrofas en comunidades microbianas bentónicas de Bahía Concepción, BCS, México. 2 records from A new species of Crinibracon Quicke (Hymenoptera: Braconidae) parasitic on pupae of Hasora chromus (Cramer) (Lepidoptera: Hesperiidae) from India. 11 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 19 records from Review of Namibimydas Hesse, 1972 and Nothomydas Hesse, 1969 (Diptera: Mydidae: Syllegomydinae: Halterorchini) with the description of new species. 542 records from Evaluación genética y demográfica de Agave victoriae-reginae T. Moore y aplicación del cultivo de tejidos para su conservación. 4549 records from Actualización de la taxonomía y distribución de los anfibios y reptiles de San Luis Potosí. 150 records from Redescription and generic placement of the spider Cryptachaea gigantipes (Keyserling, 1890) (Araneae: Theridiidae) and notes on related synanthropic species in Australasia. 1 records from Pelops occultus. 872 records from ZUEC-CRU - Coleção de Crustacea do Museu de Zoologia da UNICAMP. 25451 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 6 records from Fishes in MZNA-VERT: distribution of freshwater blenny in the Segre and Susia rivers (Spain). 829 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 2 records from Re-description of the Arctic tardigrade Tenuibiotus voronkovi (Tumanov, 2007) (Eutardigrada; Macrobiotidea), with the first molecular data for the genus. 56031 records from Cleveland Museum of Natural History.. 2 records from Cataglyphis tartessica sp. n., a new ant species (Hymenoptera: Formicidae) in southwestern Spain. 5 records from A new species of Nanochromis (Teleostei: Cichlidae) from Lake Mai Ndombe, central Congo Basin, Democratic Republic of Congo.. 1 records from Hoplophora lucida. 5313 records from Erik Acharius lichen collection. 1698 records from MNA Italica 2004_Rauschert dredge_Ross_sea_Mollusca_lgp. 33 records from Studies on Adriaphaenops Noesske with the description of five new species from the Dinarides (Coleoptera: Carabidae: Trechini). 179 records from Platyhelminth collection of National Museum of Nature and Science. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1754 records from Occurrence data of Afrotropical Mydidae (Insecta: Diptera: Asiloidea). 3000 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 34 records from The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker. 11414 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn).. 31534 records from CAS Mammalogy (MAM). 106802 records from Entomological collections, UiB. 6 records from A new genus and five new species of Astieae (Araneae: Salticidae) from Australia, with remarks on distribution. 128001 records from UMMZ Mammal Collection. 69 records from Revision of southern African species of the anglerfish genus Chaunax (Lophiiformes: Chaunacidae), with descriptions of three new species. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 1573 records from Estudios bióticos: Plantas, anfibios, mamíferos, aves y edafofauna epígea (coleópteros y arácnidos), en el complejo de páramo Los Nevados. 2205 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Actuopalynology National Collection (BAPa).. 49 records from A revision of the Neotropical tortoise beetle genus Eurypedus Gistel 1834 (Coleoptera: Chrysomelidae). 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 94 records from Scratching the surface? Taxonomic revision of the subgenus Schizoptera (Odontorhagus) reveals vast undocumented biodiversity in the largest litter bug genus Schizoptera Fieber (Hemiptera: Dipsocoromorpha). 36 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 4 records from Revision of Plumarius Philippi 1873 (Hymenoptera: Chrysidoidea, Plumariidae) from Argentina north of Patagonia, with description of eighteen new species. 2 records from Vigna pandeyana (Fabaceae), a new species from northern Western Ghats, India. 5841 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coleoptera_Types_Orient. 42 records from Collection Aves - PUM. 4129 records from Rye, Barley, Oats Genetic Resources. N.I.Vavilov Research Institute of Plant Industry, St. Petersburg. 71983 records from New Zealand Arthropod Collection (NZAC). 51 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 19 records from Distribution Data for Megachile chomskyi. 14041 records from Zooplankton Eastern Arctic Ocean Polarstern, 1995-1998. 284 records from Botanical collection of the National Museum. 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 321020 records from Centre for Biodiversity Genomics (BIOUG). 11 records from A new species of the catfish genus Akysis (Siluriformes: Akysidae) from southern Borneo.. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 202 records from The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica.. 1 records from Arthropoden aus südostalpinen Höhlen.. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 44 records from A review of the Callogobius (Teleostei: Gobiidae) from the Red Sea with the description of a new species. 150 records from Psocodea (Mallophaga) collection of National Museum of Nature and Science. 6421 records from Biodiversidad de coleópteros y arañas de las Sierras de Taxco-Huautla. 20 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 9735 records from R-Criptogamos - Herbário do Museu Nacional - Criptogamos. 6584 records from Colección de Plantas Vasculares del Herbario Forestal UDBC "Gilberto Emilio Mahecha Vega". 48658 records from Museu Paraense Emilio Goeldi - Hymenoptera Collection. 11185 records from Registros biológicos del género Piper en el herbario HUA. 2 records from Genetic evidence supports Sylvilagus mansuetus (Lagomorpha: Leporidae) as a subspecies of S. bachmani. 42619 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 4 records from A new member of the greater double-collared sunbird complex (Passeriformes: Nectariniidae) from the Eastern Arc Mountains of Africa. 1 records from Celaeno aegrota. 2 records from Zetes laevigatus. 27 records from Review of the Asian species of the subgenus Neocheilosia Barkalov (Diptera, Syrphidae), with description of new species. 827 records from Esponjas, corales escleractinios, equinodermos y peces de arrecifes coralinos del norte y sur de Veracruz. 3 records from Lectotypification of three species of Silene sect. Italicae (Rohrb.) Schischk. (Caryophyllaceae). 6 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from the Andean Cordillera of Perú with comments on relationships within the genus.. 2303 records from Lepidoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 4 records from Coping with brackish water: A new species of cave-dwelling Protosuberites (Porifera: Demospongiae: Suberitidae) from the Western Mediterranean and a first contribution to the phylogenetic relationships within the genus. 10 records from A new species of Gastrozona Bezzi (Diptera: Tephritidae: Dacinae: Gastrozonini) with an updated key to species from India. 4 records from Herpetology Collection. 3670 records from Royal Ontario Museum - Entomology (ROME). 23048 records from Herpetology Collection. 4 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 9494 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 1811 records from Western Palaearctic Ectoedemia (Zimmermannia) Hering and Ectoedemia Busck s. str. (Lepidoptera: Nepticulidae): five new species and new data on distribution, hostplants and recognition. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 1 records from FTEA. 4876 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 349178 records from AMNH Herpetology Collections. 34586 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 21312 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 1693 records from Museu de Ciències Naturals de Barcelona: MCNB-ZG. 85975 records from Mollusca specimens of Toyama Science Museum. 1724 records from Fish specimens of Natural History Museum, Kishiwada City. 1000 records from Plant specimens of Natural History Museum, Kishiwada City. 15382 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 9445 records from Invertebrate specimens in the Wakayama Prefectural Museum of Natural History, Japan.. 1200 records from Insect specimens of Natural Museum of Geihoku. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 3415 records from Plant Specimens collections of the Kyushu UNniversity Museum. 3347 records from Mammal and Fish speciemens of Kumamoto City Museum. 1 records from Zetes dorsatus. 18026 records from Herbario micológico de La Universidad de La Laguna, Tenerife: TFC_Mic. 56317 records from Fish Specimens. 16191 records from Tissues Specimens. 1815 records from RMT Trawl catch from the 1992/93 V6 KROCK voyage. 12337 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 41884 records from Museu Paraense Emilio Goeldi - Ornithology Collection - Skin. 958 records from ZFMK DORSA. 112273 records from Mammal Collection. 55 records from A review of the families and genera of the superfamily PLATYSCELOIDEA Bowman & Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea), together with keys to the families, genera and species. 34 records from Urolophus kapalensis sp. nov., a new stingaree (Myliobatiformes: Urolophidae) off eastern Australia.. 151 records from Revision of the genus Odocnemis Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from Turkey, the Caucasus and Iran with observations on feeding habits. 6174 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ichthyology National Collection (MACNIct). 14647 records from Angelo State Natural History Collections (ASNHC) - Herpetology Collection. 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 4 records from A note on Agraeciini species (Orthoptera: Tettigoniidae: Conocephalinae) in India. 6 records from Two new dolichoderine ant genera from Madagascar: Aptinoma gen. n. and Ravavy gen. n. (Hymenoptera: Formicidae).. 17 records from Donación de la base de datos resultado del diagnóstico de la diversidad de maíces nativos, su agroecosistema y sus parientes silvestres en La Chinantla. 5 records from Revision der Ceratozetidae, Ceratozetes peritus Grandjean (Arach., Acari, Oribatei). 10 records from Two new butterfly species (Lepidoptera: Rhopalocera) from Mount Cameroon, Gulf of Guinea Highlands, Cameroon. 1726 records from KTU Pinophyta. 22852 records from Natural History Museum Maastricht (NL) - Entomological Collection. 15902 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 1 records from Cepheus ovalis. 2522 records from Baillon Collection. 2 records from A new record of the genus Discoelius Latreille, 1809 (Hymenoptera: Vespidae: Eumeninae) from Northern Vietnam with description of two new species. 8853 records from Vascular Plants Collection of National Museum of Nature and Science. 18 records from Caracterización florística de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 103 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del piedemonte de Arauca, municipio de Tame. 24021 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 27777 records from UCT: South Africa Seaweeds(1905-2008). 1405 records from Computarización de la colección de moluscos holoplanctónicos del Golfo de California y Golfo de Tehuantepec. 3 records from Re-description of Cultroribula berolina Weigmann, 2006 (Acari, Oribatida, Astegistidae) from Germany with a key for the European species. 1 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 2548 records from Nuevas aportaciones a la biodiversidad de esponjas marinas de México: bases para la elaboración de código de barras de ADN. 23 records from New deep-sea Paratanaoidea (Crustacea: Peracarida: Tanaidacea) from the northeastern Gulf of Mexico. 1 records from Murcia obsoleta. 1 records from Zetes gilvulus. 7319 records from Coleoptera. 35 records from Clarification of the katydid genus Uchuca Giglio-tos, 1898 (Orthoptera: Tettigoniidae): A new species in the Brazilian Amazon Rainforest. 1347 records from Inventario de crotálidos en las zonas áridas del noroeste de México. 8880 records from Heteroptera. 14 records from A new species of Polyplocia Lestage from Malaysia with comments on the genus (Ephemeroptera, Euthyplociidae, Euthyplociinae). 39033 records from SBMNH Vertebrate Zoology. 9 records from A new species of the loricariid catfish genus Hemipsilichthys from southern Rio de Janeiro coastal rivers, southeastern Brazil (Teleostei: Siluriformes).. 458 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 4 records from Replacement names for two homonyms of Liothrips brevitubus Karny: one from California, the other for a species damaging Jatropha crops in Mexico. 44879 records from Bolus Herbarium Specimens Collection (1865-2009). 5 records from Description of a new Gibbaranea (Araneae: Araneidae) from the Western Mediterranean. 102 records from Estudio de la diversidad genética y su distribución de los maíces criollos y sus parientes silvestres en Michoacán. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 219 records from INERA-Luki reservation herbarium (CABIN project). 74 records from Description of a new Batrochoglanis species (Siluriformes, Pseudopimelodidae) from the rio Paraguai basin, State of Mato Grosso, Brazil.. 13560 records from Colección Ictiológica del Instituto Alexander von Humboldt. 24 records from Taxonomy and phylogenetic relationships among species of the seasonal, internally inseminating, South American killifish genus Campellolebias (Teleostei: Cyprinodontiformes: Rivulidae), with the description of a new species.. 29 records from Diversidad genética en dos especies mezcaleras. 3784 records from Herbier de Wallis et Futuna. 672 records from Colección de Entomología - Curculionidae. 1 records from A new species, Ceriana dirickxi (Syrphidae, Eristalinae, Cerioidini), is described and illustrated from Zimbabwe. A key to the Afrotropical species of Ceriana is given.. 4 records from A new species of Hyphessobrycon Durbin (Characiformes: Characidae) from rio Aripuanã, rio Madeira basin, Brazil. 9 records from Enigmas from the past: M’Intosh’s (1885) annelidicolous copepods from the voyage of H. M. S. Challenger. 217 records from Revision of the stag beetle genus Ryssonotus MacLeay (Coleoptera: Lucanidae), with descriptions of a new genus and three new species. 11377 records from EFC - Herbário Escola de Florestas Curitiba. 35680 records from ASE - Herbário da Universidade Federal de Sergipe. 3430 records from ZUEC-HYM - Coleção de Hymenoptera do Museu de Zoologia da UNICAMP. 6724 records from Registros ictiofaunísticos de localidades selectas de 10 regiones marinas prioritarias del Pacífico Mexicano. 5239 records from Computarización de la Colección de insectos y ácaros de importancia médica de la Facultad de Ciencias Biológicas, Universidad Autónoma de Nuevo León. 10025 records from Saltabel - Orthoptera in Belgium. 672 records from Liste taxonomique des serpents et autres reptiles du Togo. 170041 records from CM Herps Collection. 21 records from A Revision of the Pseudotropheus elongatus species group (Teleostei: Cichlidae) With Description of a New Genus and Seven New Species. 81 records from Colección de Referencia de Poliquetos del Museo de Ciencias de la Universidad El Bosque. 566 records from IPOE_Schnack_Polychaeta. 209 records from Modelación de la distribución geográfica de las especies del género Abies presentes en México. 163809 records from UEC - Herbário da Universidade Estadual de Campinas. 346 records from Packer Collection /Madagascar. 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 455 records from Especies de Anopheles en el sur de México y su distribución geográfica actual con enfoque en taxonomía clásica y molecular. 14 records from A review of the genus Mystrium (Hymenoptera: Formicidae) in the Indo-Australian region.. 92 records from Estatus de conservación de los peces dulceacuícolas del PROY-NOM-059-2000 en el noroeste de México: Sonora y Baja California. 26 records from Equinodermos de la Isla Cayo Serrana durante la Expedición Seaflower 2016. 8372 records from UWBM Herpetology Collection (Arctos). 12681 records from Colección Nacional de Paleobotánica - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 16 records from Lepidurus arcticus survey Northeast Greenland 2013. 3 records from A new species of Janusius Bretfeld, 2010 (Collembola, Sminthuridae) from the Korean Peninsula, with a key to the species of the genus. 802 records from A geographic distribution database of Mononychellus mites (Acari: Tetranychidae) on cassava (Manihot esculenta). 10191 records from Vlinderdatabank - Butterflies in Flanders and the Brussels Capital Region, Belgium. 6 records from First record of Plethus Hagen (Trichoptera, Hydroptilidae) from Japan, with description of a species. 689 records from BioBlitz Barcelona 2010-14. 42676 records from Lichen herbarium, NTNU University Museum. 2085 records from Hormigas de la transición matriz - borde - interior de bosque de Fragmentos de Bosque Seco Tropical del Valle del Cauca. 53016 records from FUEL - Herbário da Universidade Estadual de Londrina. 6868 records from Ohio State University Tetrapod Division - Mammal Collection (OSUM). 30008 records from Lepidoptera specimen database of Japan. 25397 records from MSB Parasite Collection (Arctos). 3 records from A new genus and species of Laelapidae (Acari: Mesostigmata) from Iran. 82 records from Revision of the West-Palaearctic species of the tribe Cerioidini (Diptera, Syrphidae). 3892 records from Zariquiey Collection. Biological Reference Collections ICM CSIC.. 344841 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 3 records from A new family of poecilostomatoid copepods (Strepidae fam. nov.) associated with the sun coral, Tubastraea coccinea Lesson, 1829 in Taiwan. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 222817 records from Northern Territory Museum and Art Gallery provider for OZCAM. 334 records from Listado florístico y etnobotánico de las plantas medicinales de los huicholes del río Chapalagana, Jalisco y del Nayar, Nayarit. 14 records from A study of the genus Agrilaxia Kerremans, 1903 from French Guiana (Coleoptera: Buprestidae: Anthaxiini). 176126 records from Lichen herbarium, Oslo (O). 30535 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 109270 records from ICN - Universidad Nacional de Colombia. 43 records from ZUEC-DIP - Coleção de Diptera do Museu de Zoologia da UNICAMP. 19 records from Cottus kanawhae, a new cottid fish from the New River System of Virginia and West Virginia.. 26559 records from Taiwan Forestry Research Institute. 36 records from Review of Afrotropical species of Goetheana Girault (Hymenoptera: Eulophidae), with description of a new species. 1 records from Miriapodi di alcune grotte della Campania. 9852 records from ZUEC-LEP - Coleção de Lepidoptera do Museu de Zoologia da UNICAMP. 7 records from A revision of the Aphaenogaster phalangium complex (Hymenoptera: Formicidae: Myrmicinae).. 2 records from Pseudochromis yamasakii, new species of dottyback fish from Japan (Teleostei: Pseudochromidae: Pseudochrominae). 2803 records from IMEDEA-INSECTA. 1325 records from AlgaTerra. 1763 records from BANDAPHO, BAse de DAtos sobre Aphodiidae. 890 records from RMT Trawl catch from the 2005/06 V3 BROKE-West voyage - Zooplankton. 578907 records from LACM Vertebrate Collection. 150967 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 9742 records from Natural History Museum Rotterdam (NL) - Chordata collection. 6909 records from Herbario del Departamento de Biología Vegetal (Botánica) de la Universidad de La Laguna, Tenerife (TFC). 2509 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 1667 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 27271 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 313 records from Colecciones Zoológicas de la Universidad de León, Colección de Insectos. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 577 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 1343 records from Bryophyte specimens of Iwate Prefectural Museum. 5415 records from Coleopteran specimens of Iwate Prefectural Museum. 46003 records from Vascular plant specimens of Akita Prefectural Museum. 17619 records from Akita Prefectural Museum, Insect Collection. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 8103 records from Marine Invertebrata specimens deposited in the Fukui City Natural History MUSEUM, Japan.. 1638 records from Insect Specimens deposited in the Saga Pref., Space and Science museum, JAPAN. 30117 records from Apterygota Collection of Saitama Museum of Natural History. 1129 records from Mollusca Collection of Saitama Museum of Natural History. 5538 records from Colección Alberto Tinaut (Formicidae). 173 records from Collection Crustacea NHCY. 1368 records from Collection Crustacea ZMG. 2599 records from Insecta ZMK. 1450 records from The Spider Collection at the Staatliches Museum für Naturkunde Stuttgart. 65 records from ZUEC-CNI - Coleção de Cnidaria do Museu de Zoologia da UNICAMP. 3 records from Selenops muehlmannorum spec. nov. from Southern Laos (Araneae: Selenopidae). 83 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 2587 records from Marchantiophyta / Hepatics / Liverworts of Russian Fennoscandia. 4 records from New taxa and some clarification of the tribe Steirodontini (Orthoptera: Tettigoniidae; Phaneropterinae): Tenth contribution to the suprageneric organization of Neotropical phaneropterines. 7791 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 133 records from Catalogue of type specimens of fungi and lichens deposited in the Herbarium of the University of Granada (Spain). 114 records from Contribution to the knowledge of the genus Singilis Rambur, 1837 of Africa (Coleoptera: Carabidae: Lebiini). Part IV. 127 records from ZUEC-ASC - Coleção de Ascidiacea do Museu de Zoologia da UNICAMP. 1 records from Damaeus torvus. 11169 records from Akita Prefectural Museum:Hiroki Watanabe Collection of mollusca. 43199 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 45896 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 437 records from Gymnospermatatophytina Collection of Saitama Museum of Natural History. 2777 records from Bryophyta Collection of Saitama Museum of Natural History. 1368 records from Bird Collection of Yokosuka City Museum. 15166 records from Insect Collection of Yokosuka City Museum. 4825 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 76 records from Fish (MNHM-PI). 1000 records from Diplopoda (JJHA-DI). 1643 records from Fish (ASJK-PI). 7648 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 215 records from Marine Plants (NHMC-SA). 8693 records from Insect (NSMK-IN). 1 records from Nothrus bistriatus. 2000 records from Shellfish (ASJK_MS). 4646 records from Insect (NHMK-IN). 8649 records from Fossil (WSHN-FO). 514 records from Fossil (NSMK-FO). 2777 records from Plant (KIWE-PL). 13459 records from Plant (JNHM-PL). 400 records from Insect (NHMC-IN). 5995 records from Insect (HUNM-IN). 2020 records from Birds (NHMK-BI). 1 records from Plant (MNHM-PL). 504 records from Shellfish (JNHM-MS). 15141 records from Spider (NSMK-SP). 301 records from Plant (SMNH-PL). 2420 records from Plant (NHMC-PL). 70 records from Birds (SMNH-BI). 301 records from Birds (GNHM-BI). 2894 records from Insect (SMNH-IN). 78 records from Mammals (GNHM-MM). 2050 records from Birds (ENHM-BI). 2074 records from Insect (JJHA-IN). 6067 records from Spider (YCEM-SP). 1017 records from Fish (JNHM-PI). 60 records from Mammals (NSMK-MM). 1903 records from Birds (NSMK-BI). 775 records from Insect (GNHM-IN). 30433 records from Fish (NSMK-PI). 1819 records from Plant (NSMK-PL). 25 records from Birds (MNHM-BI). 1445 records from Shellfish (GNHM-MS). 1139 records from Shellfish (MNHM-MS). 1 records from Simopone yunnanensis sp. nov. – the first record of Simopone Forel, 1891 from China (Hymenoptera, Formicidae, Cerapachyinae). 2568 records from Fish (NHMK-PI). 8551 records from Insect (ENHM-IN). 81832 records from Herbaria of the University and ETH Zürich. 2073 records from Bryophyte collection of Jyväskylä University Museum. 1309 records from Mongolian Plant (MMNH-PL). 24 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Polychaeta. 1979-80. 10928 records from TRTE Herbarium (TRTE). 319502 records from IZIKO South Africa Museum Collection (1800-2013). 609 records from Collection botanique Mulon L. (BOUM). 1330 records from Computarización sistemática de los bivalvos y gasterópodos de la sección húmeda de la Colección Malacológica Dr Antonio García-Cubas. 70 records from Revisions of Australian ground-hunting spiders. V. A new lycosoid genus from eastern Australia (Araneae: Tengellidae). 440 records from Antarctic and Subantarctic Asteroid zoogeography. 22857 records from National Botanic Garden Belgium - Myxomycetes. 6 records from A new genus of katydid from the Amazon Rainforest (Orthoptera: Tettigoniidae; Phaneropterinae; Steirodontini): Ninth contribution to the suprageneric organization of the Neotropical phaneropterines. 362 records from Museo Argentino de Ciencias Naturales (MACN), Buenos Aires: sea stars collection (Asteroidea, Echinodermata). 638 records from MNA - Sezione di Genova - (Marine Biological Samples). 1 records from On the Chilopoda from Turkey. 156 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 936 records from RMT Trawl catch from the 1982/83 V2 ADBEX I voyage. 138 records from RMT Trawl catch from the 1983/84 V5 ADBEX II voyage. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 1212 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 9494 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 34 records from Two new species of Pseudecheneis, rheophilic catfishes (Teleostei: Sisoridae) from Nepal.. 753 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 130 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Santuario de Flora y Fauna Los Colorados. 45 records from Collection Bryozoa - ZIM Hamburg. 58 records from Collection Cnidaria - ZIM Hamburg. 6840 records from Collection Crustacea - ZIM Hamburg. 1218 records from Collection Oligochaeta - ZIM Hamburg. 3229 records from Collection Polychaeta - ZIM Hamburg. 6 records from Collection Tunicata - ZIM Hamburg. 36 records from Collection Cnidaria - ZSM München. 678 records from Collection Hydrozoa - ZSM München. 94 records from Collection Bryozoa - ZMB. 343 records from Collection Cnidaria - ZMB. 28318 records from Collection Crustacea - ZMB. 665 records from Collection Echinodermata - ZMB. 127 records from Collection Hydrozoa - ZMB. 801 records from Collection Porifera - ZMB. 26573 records from Collection Vermes - ZMB. 747 records from Collection Arachnida - ZSRO. 2743 records from Collection Ornithologie - ZSRO. 2212 records from Collection Polychaeta - ZSRO. 5608 records from BANDASCA, BAse de DAtos sobre SCArabaeidae. 62210 records from Tiroler Landesmuseum Ferdinandeum. 9014 records from The Fungal Collection at the Botanische Staatssammlung München. 4 records from Bush Blitz aids description of three new species and a new genus of Australian beeflies (Diptera: Bombyliidae: Exoprosopini). 25372 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 1386 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 3028 records from The Mammalia Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 2515 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 13928 records from The Lichen Collection at the Botanische Staatssammlung München. 1515 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 2064 records from BIOTA Southern Africa - The Collection of Lichens at the Botanische Staatssammlung München. 24607 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 29805 records from Inventario florístico de los cerros San Martí y El Patol en el semidesierto queretano. 7829 records from Universidad Autónoma de Madrid, Biología, Acalypha. 2072 records from Estación Experimental de Zonas Áridas (CSIC) EEZA - Aves. 6 records from Multivariate discrimination and description of a new species of Tapinoma from the Western United States.. 2077 records from Vascular plant specimens of Iida City Museum. 2989 records from Natural History Museum Rotterdam (NL) - Invertebrata miscellaneous Collection. 8 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 8 records from Three new spider species of Anapidae (Araneae) from China. 3000 records from Marineplant (JBRI-SA). 4440229 records from Tropicos Specimen Data. 33023 records from Coleção de Entomologia do Laboratório de Biologia Vegetal. 2 records from Zorotypus weiweii (Zoraptera: Zorotypidae), a new species of angel insects, from Sabah, East Malaysia. 174 records from Collection malacologique Henri-Lecoq. 1000 records from Axel W. Erikssons African Birdcollection at Vänersborg Museum. 66157 records from Norwegian Lepidoptera working group. 13 records from A checklist of the genus Scopula (Lepidoptera: Geometridae) including description of a new species and three newly recorded species from Korea. 1818 records from Actualización de la información sobre los maíces criollos de Oaxaca. 70107 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 11981 records from SMNK Mantid Collection. 33 records from A new species and new records of Melittiini from China and Vietnam (Lepidoptera, Sesiidae). 523853 records from Western Australian Museum provider for OZCAM. 12203 records from Computarización de la Colección Nacional de Peces del Instituto de Biología UNAM. 1 records from Mesozoa - SMF. 4135 records from University of Bergen, Gastropoda. 432 records from Aschelminthes - SMF. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 67065 records from Ehime University Coleoptera Collection. 113 records from Survey of benthic and other marine invertebrates of Prydz Bay, 1990/91 Voyage 6. 61 records from Nemertini - SMF. 32 records from Hemichordata - SMF. 176 records from EDIT - ATBI in Spreewald (Germany). 26 records from Echiura - SMF. 361 records from Water mite collection of Pauli Bagge. 1323 records from Estación Experimental de Zonas Áridas (CSIC), Almería: EEZA-Ungulados. 3 records from On a new marine podocopid genus and species (Ostracoda: Hemicytheridae) from Brazil. 41 records from Integrative taxonomic re-description of Halisarca magellanica and description of a new species of Halisarca (Porifera, Demospongiae) from Chilean Patagonia. 84 records from Taxonomic revision of the Neotropical Myrmicinae ant genus Blepharidatta Wheeler. 53 records from Squid collection from 1995/96 V4 BROKE. 22 records from Geophagus abalios, G. dicrozoster and G. winemilleri (Perciformes: Cichlidae), three new species from Venezuela.. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 1574 records from Lepidoptera - SNSD. 205668 records from SysTax - Zoological Collections. 174 records from Birds (NHCA-BI). 35 records from The Peacock Spiders (Araneae: Salticidae: Maratus) of the Queensland Museum, including six new species. 122 records from Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr).. 4 records from Neolamprologus devosi sp. n., a new riverine lamprologine cichlid (Teleostei, Cichlidae) from the lower Malagarasi River, Tanzania.. 11 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 42 records from Chaetognatha - SMF. 16 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 8 records from Phoronida - SMF. 1240 records from Sponge collection of National Museum of Nature and Science. 1001 records from Naturhistorisches Museum Mainz, Botanical Collection. 9038 records from Naturhistorisches Museum Mainz, Zoological Collection. 2 records from Re-description of the Arctic tardigrade Tenuibiotus voronkovi (Tumanov, 2007) (Eutardigrada; Macrobiotidea), with the first molecular data for the genus. 2775 records from CeDoc de Biodiversitat Vegetal: BCN- Algues de J. Rodríguez Femenías. 320 records from Myxomycetes collection of the University of Eastern Finland. 16604
Keywords: GBIF; biodiversity; species occurrences